STARTING MATERIAL USED IN VAPOR DEPOSITION PROCESS FOR GROWING SiC BOULE
Patent Information
- Application Number
- JP2024202887
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2017-08-14
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-19
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
【0052】 さらに、蒸着装置内でブールを成長させる方法が提供される。この方法は、極めて純度の高い炭化ケイ素粒子とバインダーとの複合材料の体積形状物であって、炭化ケイ素は非酸化物形成表面を有するポリマー由来の炭化ケイ素粒子で少なくとも99.9999%の純度を有し、バインダーは炭化ケイ素粒子を結合し、それによって体積形状物を規定するものであり、シリコン、炭素、およびブールに機能性を提供するための添加剤を含み、ポリマー由来の炭化ケイ素粒子の揮発温度以下の揮発温度を有し、添加剤は、ポリマー由来のセラミック粒子のほぼ揮発温度の揮発温度を有する体積形状物を蒸着装置内に配置し、該体積形状物を蒸発させて蒸気を形成し、基板上に蒸気を堆積させてブールを形成する。バインダーはブールに所定の機能性を提供することができず、添加剤が一部機能性を提供することができる。
Smart Images

Figure 2025024179000001_ABST
Abstract
Description
[Technical field]
[0001] Related Applications This application: (I) claims the benefit under 35 U.S.C. § 119(E) of U.S. Provisional Application No. 62 / 478,383, filed (1) on March 29, 2017, and (II) claims the benefit under 35 U.S.C. § 119(E) of U.S. Provisional Application No. 62 / 545,367, filed (1) on August 14, 2017, the disclosures of each of which are incorporated herein by reference in their entireties.
[0002] The present invention relates to silicon carbide (SiC) and SiC compounds, structures, components, materials, and apparatus and methods for producing the same, and more particularly to SiC volumetric shapes, the use of these to form boules in a deposition process, and related methods.
[0003] Polysilocarb materials and methods of making those materials are disclosed and taught in U.S. Pat. Nos. 9,815,952 and 9,815,943, and U.S. Patent Publication No. 2015 / 0175750, the disclosures of each of which are incorporated herein by reference in their entireties. [Background technology]
[0004] As used herein, unless otherwise indicated, "vapor deposition" (VD), "vapor deposition techniques", vapor deposition processes and similar terms are used in their broadest sense and include, for example, processes in which a solid or liquid starting material is converted to a gaseous or vapor state and the gas or vapor is then deposited to form (e.g., grow) a solid material. As used herein, vapor deposition techniques include growth by epitaxy, where a layer is provided from a vapor or gas phase. Other types of vapor deposition techniques include chemical vapor deposition (CVD), physical vapor deposition (PVD), plasma enhanced CVD, physical vapor transport (PVT), and the like. Examples of vapor deposition equipment include hot wall reactors, multi-wafer reactors, chimney reactors, RF furnaces, and boule growth furnaces.
[0005] As used herein, unless otherwise indicated, the term "vaporization temperature" is to be given its broadest possible meaning and includes the very small range of temperatures at which a material transitions from a liquid to a gaseous state, a solid to a gaseous state, or both (e.g., transitions from solid to liquid to gas) occur, e.g., below about 20°C, below about 10°C, and below about 5°C. Unless otherwise indicated, the vaporization temperature corresponds to a particular pressure, e.g., 1 atmosphere, 0.5 atmosphere, at which such transition occurs. When discussing the vaporization temperature of a material used in a particular application, method, or device, such as a PVT device, the vaporization temperature is at the pressure used or typically used in that application, method, or device, unless otherwise indicated.
[0006] Silicon carbide generally does not have a liquid phase, but instead sublimes at temperatures above about 1,700°C under vacuum. In FIG. 17, a chart of the partial pressure curve for SiC is shown. Typically, in industrial and commercial applications, conditions are established such that sublimation occurs at temperatures above about 2,500°C. When silicon carbide sublimes, a vapor is formed that is typically composed of various types of silicon and carbon, e.g., Si, C, SiC, Si2C, SiC2. It has generally been thought that temperature determines the ratio of these different components in silicon carbide vapor. However, the present invention provides, among other things, the ability to preselect and control the ratio of these components independent of or in conjunction with temperature.
[0007] As used herein, unless otherwise specified, the term specific gravity, also called apparent density, shall mean in the broadest possible sense, generally the weight per unit volume of a structure, e.g., a volumetric form of material. It includes the internal porosity of the particle as a fraction of the volume. It can be measured, among other techniques, with a low viscosity fluid that wets the particle surface.
[0008] As used herein, unless otherwise specified, the term actual density, which may also be referred to as true density, is used in its broadest sense to mean the typical average weight per unit volume of a material when no voids are present in the material. This measurement and property essentially excludes internal porosity from the material, i.e., does not include voids.
[0009] Therefore, a collection of porous foam balls (such as NERF® balls) can be used to demonstrate the relationship between the three density properties: The weight of the balls filling a container is the bulk density of the balls. Bulk density = (weight of ball) / (volume of container)
[0010] The weight of a single ball per spherical volume of the ball is its apparent density. Apparent density = (weight of one ball) / (volume of that ball)
[0011] The weight per volume of material that makes up the ball's skeleton, i.e., the ball with all void volume removed, is its actual density. Actual Density = (weight of material) / (volume of material without voids)
[0012] As used herein, unless otherwise specified, room temperature is 25° C., and standard ambient temperature and pressure are 25° C. and 1 atmosphere. All tests, test results, physical properties, and temperature-dependent values, pressure-dependent values, or both, are at standard ambient temperature and pressure (which may include viscosity) unless otherwise specified.
[0013] As a general guide, the term "about" and the symbol "~" are used herein to mean, unless otherwise specified, to encompass a variation or range of ±10%, the experimental or instrumental error associated with obtaining the stated value, and preferably the greater of these.
[0014] As used herein, unless otherwise specified, %, weight %, and mass % are used interchangeably and the weight of a first component is referred to as a percent of, for example, a formulation, mixture, preform, material, structure, or product. X / Y or XY indicates the weight % of X and the weight % of Y in a formulation, unless otherwise specified. X / Y / Z or XYZ indicates the weight % of X, the weight % of Y, and the weight % of Z in a formulation, unless otherwise specified.
[0015] As used herein, unless otherwise specified, "volume percent" and "% volume" and similar such terms refer to the volume of a first component as a percentage of the volume of, for example, a formulation, mixture, preform, material, structure, or product.
[0016] As used herein, unless otherwise indicated, the terms "source material" and "starting material" are synonymous and should be given the broadest possible definition as used in the context of boule growth, deposition apparatus, epitaxy, and crystal growth and deposition processes, and should refer to the materials, volumetric shapes, and both that are placed in a growth chamber or apparatus for crystal growth, boule growth, epitaxy, or SiC deposition, and that create a flux.
[0017] As used herein, unless otherwise indicated, the terms "existing materials," "prior materials," "current materials," "currently available materials," "existing deposition equipment," "current deposition equipment," and similar terms refer to source materials and equipment that are or were in existence prior to the present invention. Use of the terms is not an admission of prior art; it merely describes the current state of the art as a baseline or reference point against which significant and dramatic improvements of embodiments of the present invention may be evaluated, contrasted, and measured.
[0018] The Background of the Invention section is intended to introduce various aspects of technology that may be related to embodiments of the present invention. As such, the preceding discussion in this section is intended to provide a framework for better understanding the present invention and should not be construed as admissions of prior art. Summary of the Invention [Problem to be solved by the invention]
[0019] There has long been a need for a cost-effective method of producing SiC boules to provide high quality single crystal SiC boules for use in the manufacture of SiC electronic components for devices, apparatus, and equipment. The present invention solves this need by, among other things, providing the depositions, materials, articles of manufacture, devices, and processes taught, disclosed, and claimed herein. [Means for solving the problem]
[0020] According to the present invention, there is provided a method for making volumetric shapes of SiC, including polymer derived SiC, using a binder. In this case, polymer derived SiC particles are mixed with a binder material, and the binder and SiC particles are formed and cured into a volumetric shape, preferably having a predetermined shape and size (and therefore volume). The volumetric shapes and binder can then be used, for example, in a deposition process to form materials, layers and structures, such as boules. Examples of apparatus and processes in which the present invention can be used are disclosed and taught in U.S. Patent Application Publication No. 2017 / 0204532.
[0021] Thus, a volume shape of SiC is provided, the volume shape having about 100 g to about 12,000 g of SiC granules having a particle size of about 0.1 μm to about 100 μm. The SiC granules have a volume shape with structural integrity, and the binder binding the SiC granules is capable of maintaining its structural integrity when the volume shape is placed in a deposition apparatus during a boule growth cycle. The volume shape in this case is void, porous, and has an apparent density of less than 3.0 g / cc.
[0022] The present invention further provides these methods, volume shapes, wafers and boules having one or more of the following characteristics: the weight of the SiC granules is from about 1000 g to about 9000 g; the weight of the SiC granules is from about 2500 g to about 8000 g; the weight of the SiC granules is from about 5000 g to about 11000 g; the SiC granules have a primary particle size D of from about 0.1 μm to about 20.0 μm; 50 Size: SiC granules are primary particles of about 0.5 μm to about 10.0 μm. 50 Size: SiC granules are primary particles of about 0.5 μm to about 2.0 μm. 50 Size: SiC granules are primary particles of about 1 μm to about 5 μm. 50 Size: SiC granules are primary particles of about 0.5 μm to about 3 μm. 50Size; the void defines a channel in the top of the volumetric shape; the void defines an angled annular channel in the top of the volumetric shape; the void is located in the top of the volumetric shape; the void is located in the bottom of the volumetric shape; the void is located in the top and bottom of the volumetric shape; the void defines a cylindrical channel extending through the volumetric shape; the volumetric shape is a puck and has a flat top, a flat bottom, and tapered sides; apparent density is less than 2.5 g / cc; apparent density is less than 2.5 g / cc; apparent density is less than 2.5 g / cc; apparent density is about 1.5g / cc to 2.8g / cc; about 1.5g / cc to 2.8g / cc; the SiC granules are polymer derived SiC and have a purity of at least 99.999%; the SiC granules are polymer derived SiC and have a purity of at least 99.9999%; a molar ratio of Si:C of 0.5:2; a molar ratio of Si:C of 2:0.5; a molar ratio of Si:C in the range of about 1:1 to about 0.5:2; a molar ratio of Si:C in the range of about 1:1 to about 2:0.5; a molar ratio of Si:C in the range of about 0.5:2 to about 2:0.5.
[0023] The present invention further provides a volume shape comprising about 100 g to about 12,000 g of SiC granules having a particle size of about 0.1 μm to about 100 μm, the SiC granules having structural integrity and capable of maintaining structural integrity when placed in a deposition apparatus during a boule growth cycle, the volume shape being porous with one void and having an apparent density of less than 3.0 g / cc.
[0024] The present invention further provides a structurally intact volume shape comprising about 100 g to about 12,000 g of SiC granules having a particle size of about 0.1 μm to about 100 μm and a binder, the binder binding the SiC granules together such that the volume shape maintains its structural integrity when placed in a deposition apparatus during a boule growth cycle, the volume shape having one void.
[0025] The present invention further provides a volume shape made of SiC granules, the SiC granules having a particle size of about 0.1 μm to about 100 μm that provides structural integrity for the volume shape, and a binder that binds the SiC granules, such that the volume shape can maintain structural integrity when placed in a deposition apparatus during a boule growth cycle. The volume shape has one void, is not porous, and has an apparent density of less than 3.1 g / cc. The volume shape provides a predetermined flux during a boule growth cycle.
[0026] The invention further provides methods, volumetric shapes, wafers, and boules having one or more of the following characteristics: the predetermined flux is a uniform and consistent flux; has an increased flux density near the outer region of the growth surface of the boule during the last 20% of the growth cycle; has an increased flux density near the outer region of the growth surface of the boule during the last 30% of the growth cycle; has an increased flux density near the outer region of the growth surface of the boule during the last 40% of the growth cycle.
[0027] The present invention further provides a volume shape comprising SiC granules having a particle size of about 0.1 μm to about 100 μm and forming the structural integrity of the volume shape, the volume shape having one void, being porous, the volume shape having an apparent density of less than 3.1 g / cc, and capable of providing a predetermined flux during a growth cycle.
[0028] The present invention further provides a volume shape having SiC granules with a particle size of about 0.1 μm to about 100 μm forming the structural integrity of the volume shape and a binder binding the SiC granules together such that the volume shape is capable of maintaining structural integrity when placed in a deposition apparatus during a boule growth cycle, the volume shape having one void and capable of providing a predetermined flux.
[0029] The present invention further provides a volume shape having about 100 g to about 12,000 g of SiC granules having a particle size of about 0.1 μm to about 100 μm forming the volume shape, the volume shape being porous and the volume shape having an apparent density of less than 2.9 g / cc, the volume shape being capable of providing a consistent rate of flux formation during the growth cycle when placed in a deposition apparatus during a boule growth cycle.
[0030] The present invention further provides a volume shape formed from about 100 g to about 12,000 g of SiC granules having a particle size of about 0.1 μm to about 100 μm, the volume shape having one void, the volume shape being capable of providing a consistent rate of flux formation during the boule growth cycle when placed in a deposition apparatus during the boule growth cycle.
[0031] The present invention further provides a volume shape having about 100 g to about 12,000 g of SiC granules having a particle size of about 0.1 μm to about 100 μm and a binder for binding the SiC granules, the volume shape being capable of providing a predetermined flow rate of flux formation during the growth cycle when placed in a deposition apparatus during the growth cycle of the boule.
[0032] The present invention further provides a volume shape having about 100 g to about 12,000 g of SiC granules having a particle size of about 0.1 μm to about 100 μm and a binder binding the SiC granules together, the volume shape being porous and having an apparent density of less than 2.9 g / cc, and capable of providing uniform flux formation during the growth cycle when placed in a deposition apparatus during the boule growth cycle.
[0033] Further provided is a volumetric shape having about 100 g to about 12,000 g of SiC granules having a particle size of about 0.1 μm to about 100 μm, the volumetric shape having one void and being capable of providing uniform flux formation during the growth cycle when placed in a deposition apparatus during the boule growth cycle.
[0034] Further provided is a volume shape having about 100 g to about 5,000 g of SiC granules having a particle size of about 0.1 μm to about 100 μm and a binder for binding the SiC granules, the volume shape being capable of providing a uniform flux formation during the growth cycle when placed in a deposition apparatus during the growth cycle of the boule.
[0035] The present invention further provides a method of growing a SiC boule by placing a starting material having SiC in a deposition apparatus and heating the starting material to a temperature at which the SiC sublimes to form a flux of Si and C that flows through a region immediately adjacent a growth surface of the boule, where the area of the region is the same as and coincident with the growth surface of the boule, the flux being predetermined over the entire region and depositing the flux on the growth surface of the boule to grow the length of the boule.
[0036] The invention further provides these methods, volumetric shapes, wafers, and boules having one or more of the following characteristics: the flux is uniform throughout the area during boule growth; the flux is greater near the outer area of the face of the boule when at least half the length of the boule is grown during boule growth; the growth face of the boule is a seed crystal; the growth face of the boule is a face of the boule; the grown boule is a single crystal; the grown boule is of a single polytype; whereby the grown boule has a diameter of about 3 inches to about 6 inches, a length of about 2 inches to about 8 inches, and a radius of curvature of the growth face of the boule is at least twice the length; ... inch diameter, about 2 inches to about 8 inches long, and a radius of curvature of the growth surface of the boule at least 5 times the length; grown boules about 3 inches to about 6 inches diameter, about 2 inches to about 8 inches long, and a radius of curvature of the growth surface of the boule at least 10 ...50 inches; grown boules about 3 inches to about 6 inches diameter, about 2 inches to about 8 inches long, and a radius of curvature of the growth surface of the boule at least 50 inches; The boule is about 6 inches to about 8 inches in diameter, about 2 inches to about 8 inches in length, and the radius of curvature of the growth surface of the boule is at least twice as long; the grown boule is about 6 inches to about 8 inches in diameter, about 2 inches to about 8 inches in length, and the radius of curvature of the growth surface of the boule is at least 5 times as long; the grown boule is about 6 inches to about 8 inches in diameter, about 2 inches to about 8 inches in length, and the radius of curvature of the growth surface of the boule is at least 10 .... the grown boule is characterized by a diameter of about 6 inches to about 8 inches, a length of about 2 inches to about 8 inches, and a radius of curvature of the growth surface of the boule of at least about 50 inches; the grown boule is characterized by a length of about 2 inches to about 8 inches, and the radius of curvature of the growth surface of the boule is at least twice the length; the grown boule is characterized by a length of about 2 inches to about 8 inches, and the radius of curvature of the growth surface of the boule is at least 5 times the length; the grown boule is characterized by a length of about 2 inches to about 8 inches, and the radius of curvature of the growth surface of the boule is at least 10 times the length;The grown boule is characterized by having a length of about 2 inches to about 8 inches and a radius of curvature of the growth face that is infinite; the grown boule is characterized by a length of about 2 inches to about 8 inches and a radius of curvature of the growth face that is at least about 50 inches; the flux is maintained at a constant rate;
[0037] The invention further provides a method of growing a SiC boule comprising placing a starting material having SiC in an evaporation apparatus, heating the starting material to generate a flux, initiating a growth cycle, flowing the flux to an area immediately adjacent a growth surface of the boule during the growth cycle, maintaining the flux flow at a predetermined rate during the growth cycle, and depositing the flux on the growth surface of the boule to grow a length of the boule.
[0038] The invention further provides a method for growing a SiC boule by placing a volume shape of starting material having SiC in an evaporation apparatus, heating the volume shape to produce a directional flux during a growth cycle of the boule, and depositing the directional flux on a growth surface of the boule to grow the length of the boule.
[0039] Additionally, the present invention provides methods, volumetric shapes, wafers and boules having one or more of the following features: providing an increased flux density in a directional flux to an outer region of the growth surface, such that the boule has a flat surface;
[0040] Additionally, the present invention provides these methods, volume features, wafers and boules having one or more of the following features: a boule grown by the methods disclosed herein; a method of manufacturing an electronic component comprising obtaining a wafer produced by the methods disclosed herein; providing a printed circuit on a wafer made by the methods disclosed herein; creating a system having an electronic component obtained by the methods disclosed herein; assembling into a system an electronic component based on or including a wafer made by the methods disclosed herein.
[0041] Further provided is a method for providing a large number of devices from a single growth cycle of a boule, the method including: placing a volume shape of starting material having SiC in a deposition apparatus, heating the volume shape to provide a directional flux during a growth cycle of the boule, and depositing the directional flux on a growth surface of the boule to grow the length of the boule, which can provide a large number of wafers, electronic circuits, and systems.
[0042] Additionally provided are methods, volume shapes, wafers and boules having one or more of the following characteristics: about 80% of the length of the boule is such that it can be cut to provide defect-free wafers; about 90% of the length of the boule is such that it can be cut to provide defect-free wafers; about 95% of the length of the boule is such that it can be cut to provide defect-free wafers; about 99% of the length of the boule is such that it can be cut to provide defect-free wafers, the wafers having MPD (≦0.1 cm-2), TSD (≦300 cm-2), and BPD (≦500 cm-2); a resistivity greater than about 10,000 ΩM-cm at 20° C.; a resistivity equal to or greater than about 10,000 Ω-cm at 20° C.
[0043] Further provided is a volume shape of a composite of ultra-pure silicon carbide particles and a binder for use in vapor deposition growth of a silicon carbide boule, the volume shape comprising silicon carbide particles of at least 99.999% purity, a binder binding the silicon carbide particles together and thereby defining the volume shape, the binder comprising a crosslinked polymeric material comprised of carbon and silicon, the binder having a volatilization temperature of between about 300° C. and 700° C. such that it does not impede the growth of the SiC boule and does not adversely affect the quality of the SiC boule.
[0044] Additionally provided are methods, volume shapes, wafers and boules having one or more of the following characteristics: density of about 1 g / cc to about 3 g / cc; binder is less than 5% of the volume shape's weight; binder is less than 10% of the volume shape's weight; binder is less than 20% of the volume shape's weight; binder is less than 35% of the volume shape's weight; binder is less than 5% of the volume shape's weight; binder is less than 10% of the volume shape's weight; binder is less than 20% of the volume shape's weight; binder is less than 35% of the volume shape's weight; density less than about 3.1 g / cc; density less than about 3 g / cc; density less than about 2.5 g / cc; density less than about 2 g / cc.
[0045] Additionally, there is provided a volume shape of a composite of ultra-pure silicon carbide particles and a binder for use in vapor deposition growth of a silicon carbide boule, the volume shape comprising polymer-derived silicon carbide particles of at least 99.9999% purity having a non-oxide forming surface, a binder binding the silicon carbide particles together and thereby defining the volume shape, the binder having a volatilization temperature lower than the volatilization temperature of the polymer-derived silicon carbide particles, which does not interfere with the growth of the SiC boule and which cannot adversely affect the quality of the SiC boule.
[0046] Additionally provided are methods, volume shapes, wafers and boules having one or more of the following features: a void volume porosity of about 10% to about 30%; a void volume porosity of about 5% to about 40%; a void volume porosity of about 10% to about 30%; a void volume porosity of about 5% to about 40%; a density of about 1 g / cc to about 3 g / cc; the binder is less than 5% by weight of the volume shape; the binder is less than 10% by weight of the volume shape; the binder is less than 20% by weight of the volume shape; or less than 35% by weight of the volume shape.
[0047] Additionally provided are methods, volume shapes, wafers, and boules having one or more of the following features: the volatilization temperature of the binder is at least 500° C. lower than the volatilization temperature of the silicon carbide particles; at least 550° C. lower than the volatilization temperature of the silicon carbide particles; at least 600° C. lower than the volatilization temperature of the silicon carbide particles; the volatilization temperature of the binder is at least 650° C. lower than the volatilization temperature of the silicon carbide particles; the volatilization temperature of the binder is at least 700° C. lower than the volatilization temperature of the silicon carbide particles; at least 800° C. lower than the volatilization temperature of the silicon carbide particles; the volatilization temperature of the binder is at least 900° C. lower than the volatilization temperature of the silicon carbide particles; at least 1,000° C. lower than the volatilization temperature of the silicon carbide particles.
[0048] Further provided is a volume shape of a composite material of ultra-pure silicon carbide particles and a binder for use in vapor deposition growth of silicon carbide boules, the volume shape comprising silicon carbide particles having at least a particle diameter of about 0.1 mm to about 20.0 mm. 50 silicon carbide particles having a particle size and a purity of 99.999%; a binder that binds the silicon carbide particles together and thereby defines a volumetric shape, the binder comprising a crosslinked polymeric material having carbon and silicon, having a volatilization temperature of between about 300° C. and 900° C., and that is incapable of impeding boule growth and incapable of adversely affecting boule quality.
[0049] Additionally, methods, volume shapes, wafers and boules are provided having one or more of the following characteristics: an elastic modulus of about 10 GPa to about 300 GPa; 2 to about 2,000 kg / mm 2 Hardness: about 50MPa to about 3,000MPa Compressive strength: about 300Kg / mm 2 ~ approx. 2,000 kg / mm 2 Hardness: Approx. 50MPa to 3,000MPa compressive strength; D for particles from 0.5mm to 10mm 50 Particle size: D with particles between about 1 mm and about 15 mm 50 D with a particle size of about 1 mm 50 Particle size: Particles have a diameter of about 3 mm 50 Particle size.
[0050] Further provided is a volume shape of a composite of ultra-pure silicon carbide particles and a binder for use in vapor deposition growth of a silicon carbide boule, the volume shape comprising: silicon carbide particles of at least 99.999 purity having an average particle size of 5 mm or less, with 10% or less of the particles being larger than 10 mm; a binder binding the silicon carbide particles together thereby defining the volume shape, the binder comprising a crosslinked polymeric material having carbon and silicon, and having a volatilization temperature of between about 300° C. and 900° C. such that the binder is unable to impede the growth of the boule and is unable to adversely affect the quality of the boule.
[0051] Additionally, a method is provided for growing a boule in a vapor deposition apparatus by placing the volume shape of the present invention in the vapor deposition apparatus, first vaporizing the binder, then vaporizing the silicon carbide particles, and forming a vaporized binder-free boule from the vaporized silicon carbide particles.
[0052] Also provided is a method of growing a boule in a deposition apparatus, comprising placing a volumetric shape of a composite of highly pure silicon carbide particles and a binder, the silicon carbide being polymer-derived silicon carbide particles having a non-oxide forming surface and having a purity of at least 99.9999%, the binder binding the silicon carbide particles and thereby defining the volumetric shape, including silicon, carbon, and an additive for providing functionality to the boule, the additive having a volatilization temperature below the volatilization temperature of the polymer-derived silicon carbide particles, the additive having a volatilization temperature about the volatilization temperature of the polymer-derived ceramic particles, in a deposition apparatus, evaporating the volumetric shape to form a vapor, and depositing the vapor on a substrate to form a boule, the binder being unable to provide the desired functionality to the boule and the additive being able to provide some functionality.
[0053] Further provided is a volume shape of a composite material of ultra-pure silicon carbide particles and a binder for use in vapor deposition growth of a silicon carbide boule. The volume shape has silicon carbide particles of at least 99.999% purity; a binder binding the silicon carbide particles together and thereby defining the volume shape. The binder is an oxygen-free, carbon- and silicon-containing crosslinked polymeric material and has a volatilization temperature of between about 300° C. and 800° C. such that the binder does not interfere with the growth of the SiC boule and is unable to adversely affect the quality of the SiC boule.
[0054] Further provided is a volume shape of a composite of ultra-pure silicon carbide particles and a binder for use in vapor deposition growth of a silicon carbide boule, the volume shape comprising silicon carbide having at least 99.999% purity; a binder binding the silicon carbide particles to define the volume shape; the binder comprising a cross-linked polymeric material that is oxygen and silicon free and includes carbon; and the binder has a volatilization temperature of between about 300° C. and 800° C. such that the binder does not interfere with the growth of the SiC boule or adversely affect the quality of the SiC boule.
[0055] [Brief description of the drawings]
[0056] [Figure 1A] FIG. 1 is a perspective view of one embodiment of a volumetric shape of the present invention (6 inch diameter, flat top and bottom).
[0057] [Figure 1B] FIG. 1B is a top perspective view of the embodiment of FIG. 1A.
[0058] [Figure 1C] FIG. 1B is a side view of the embodiment of FIG. 1A.
[0059] [Figure 1D] FIG. 1B is a top view of the embodiment of FIG. 1A.
[0060] [Figure 2A] FIG. 1 is a top perspective view of an embodiment of a volumetric shape according to the present invention (4½ inch diameter, partial central cylindrical open top).
[0061] [Figure 2B] FIG. 2B is a side perspective view of the embodiment of FIG. 2A.
[0062] [Figure 2C] FIG. 2B is a top view of the embodiment of FIG. 2A.
[0063] [Figure 2D] FIG. 2C is a schematic cross-sectional view of an embodiment of the general type shown in FIGS. 2A to 2C.
[0064] [Figure 3A] 1 is a perspective view of an embodiment of a volume shape according to the invention; FIG.
[0065] [Figure 3B] FIG. 3B is a side perspective view of the embodiment of FIG. 3A.
[0066] [Figure 3C] FIG. 3B is a top view of the embodiment of FIG. 3A.
[0067] [Figure 3D] FIG. 6 is a cross-sectional perspective view of the embodiment of FIG. 3A.
[0068] [Figure 3E] FIG. 6 is a side view of the cross section of FIG. 3A.
[0069] [Figure 3F] FIG. 3C is a schematic cross-sectional view of an embodiment of the general type shown in FIGS. 3A and 3E.
[0070] [Figure 4A] FIG. 1 is a perspective view of an embodiment of a volumetric shape according to the present invention (a tapered cylinder with an angled annular channel at the top).
[0071] [Figure 4B] FIG. 4B is a side perspective view of the embodiment of FIG. 4A.
[0072] [Figure 4C] FIG. 4B is a side perspective view of the embodiment of FIG. 4A.
[0073] [Figure 4D] FIG. 4B is a top view of the embodiment of FIG. 4A.
[0074] [Figure 4E] FIG. 4B is a side perspective view of a cross section of the embodiment of FIG. 4A.
[0075] [Figure 4F] 4A-4E are schematic cross-sectional views of embodiments of the general type shown in FIG.
[0076] [Figure 5A] FIG. 2 is a top view of an embodiment of a volumetric shape according to the present invention (a tapered cylinder with the top and bottom cut off).
[0077] [Figure 5B] FIG. 5B is a bottom view of the embodiment of FIG. 5A.
[0078] [Figure 5C] FIG. 5B is a perspective view of a cross section of the embodiment of FIG. 5A.
[0079] [Figure 5D] FIG. 5B is a cross-sectional side view of the embodiment of FIG. 5A.
[0080] [Figure 5E] FIG. 5B is a cross-sectional side view of the embodiment of FIG. 5A.
[0081] [Figure 5F] FIG. 5B is a schematic cross-sectional view of an embodiment of the general type shown in FIGS. 5A-5C.
[0082] [Figure 6A] FIG. 1 is a bottom perspective view of one embodiment of a volumetric shape according to the present invention (tapered cylinder bottom cutaway).
[0083] [Figure 6B] FIG. 6B is a bottom view of the embodiment of FIG. 6A.
[0084] [Figure 6C] FIG. 6B is a side perspective view of the embodiment of FIG. 6A.
[0085] [Figure 6D] FIG. 56 is a schematic cross-sectional view of an embodiment of the general type shown in FIGS. 56-6C.
[0086] [Figure 7] 1 is a schematic cross-sectional view of one embodiment of a volume shape according to the present invention;
[0087] [Figure 8] 1 is a schematic cross-sectional view of one embodiment of a volume shape according to the present invention;
[0088] [Figure 9] 1 is a schematic cross-sectional view of one embodiment of a volume shape according to the present invention;
[0089] [Figure 10] 1 is a schematic cross-sectional view of one embodiment of a volume shape according to the present invention;
[0090] [Figure 11] 1 is a schematic cross-sectional view of one embodiment of a volume shape according to the present invention;
[0091] [Figure 12] 1 is a schematic cross-sectional view of one embodiment of a volume shape according to the present invention;
[0092] [Figure 13] 1 is a schematic cross-sectional view of one embodiment of a volume shape according to the present invention;
[0093] [Figure 14] 1 is a schematic cross-sectional view of one embodiment of a volume shape according to the present invention;
[0094] [Figure 15] 1 is a schematic cross-sectional view of one embodiment of a volume shape according to the present invention;
[0095] [Figure 16] FIG. 2 is a process flow diagram of an embodiment of the system and method according to the present invention.
[0096] [Figure 17] 1 is a partial pressure curve of SiC, Si2C, and SiC2.
[0097] [Figure 18] 1 is a schematic cross-sectional view of a deposition apparatus and process according to the present invention;
[0098] [Figure 19] 1 is a chart illustrating an embodiment of boule growth rate in accordance with the present invention.
[0099] [Figure 20A] FIG. 1 is a top perspective view of a volumetric shape according to the present invention (tapered cylinder, no cutouts, flat bottom and top).
[0100] [Figure 20B] FIG. 20B is a top perspective view of the volumetric shape of FIG. 20A.
[0101] [Figure 20C] FIG. 20B is a side perspective view of the volumetric shape of FIG.
[0102] [Figure 21] 1 is a schematic diagram of an embodiment of a boule illustrating the determination of the radius of curvature of the boule surface.
[0103] To the extent that a ruler is shown in a figure, it provides a measure of that figure's embodiment and its features. The ruler is used for illustrative purposes and is not intended to limit the embodiments to other sizes, shapes, and proportions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0104] Generally, the present invention relates to volume shapes of silicon carbide (SiC) particles and growing structures from these volume shapes. In embodiments, the particles, as well as the volume shapes, have good, high, and ultra-high purity. The present invention further relates to an apparatus and method for using these SiC particle volume shapes in deposition techniques to form SiC boules, which are used, for example, to make wafers and devices for electronics applications.
[0105] Although this specification focuses on SiC deposition techniques, it should be understood that the invention is not so limited and may find applicability to other SiC crystal growth processes, bonding processes, and other applications.
[0106] Embodiments can generally include polymer derived ceramics ("PDCs"), products and applications that use, are based on, or comprise PDCs.
[0107] The embodiments of the present invention preferably use, are based on, or consist of "polysilocarb" materials, such as PDC, which is a material containing silicon (Si), oxygen (O), and carbon (C), and which have been cured, pyrolyzed, and converted to SiC. The polysilocarb materials can be of high purity, ultra-high purity. The polysilocarb materials can contain other elements. The polysilocarb materials are made from one or more polysilocarb precursor formulations or precursor formulations. The polysilocarb precursor formulations include one or more functionalized silicon polymers, or monomers, non-silicon based crosslinkers, and potentially other components, such as inhibitors, catalysts, fillers, dopants, modifiers, initiators, reinforcing agents, fibers, particles, colorants, pigments, dyes, the same or other PDCs, ceramics, metals, metal complexes, and combinations and variations of these and other materials and additives. Silicon oxycarbide materials, SiOC formulations, and similar terms, unless otherwise specified, refer to polysilocarb materials and include liquid materials, solid uncured materials, cured materials, ceramic materials, and combinations and variations thereof.
[0108] Examples of PDCs, PDC formulations, potential precursors, starting materials, and apparatus and methods for making these materials that may be improved, adapted, or used using the teachings herein can be found in, for example, U.S. Patent Publications 2014 / 0274658, 2014 / 0323364, 2015 / 0175750, 2016 / 0207782, 2016 / 0280607, 2017 / 0050337, 2008 / 0095942, 2008 / Nos. 20093185, 2007 / 0292690, 2006 / 0069176, 2006 / 0004169, and 2005 / 0276961, as well as U.S. Pat. Nos. 9,499,677, 9,481,781, 8,742,008, 8,119,057, 7,714,092, 7,087,656, 5,153,295, and 4,657,991, the entire disclosures of each of which are incorporated herein by reference.
[0109] Various polysilocarb formulations, processes, methods of manufacture, and formulations are described in U.S. Patent Nos. 9,499,677, 9,481,781 and U.S. Patent Publication Nos. 2014 / 0274658, 2014 / 0323364, 2015 / 0175750, 2016 / 0207782, 2016 / 0280607, and 2017 / 0050337, the entire disclosures of each of which are incorporated herein by reference.
[0110] Typically, and preferably, the polysilocarb precursor formulation is initially liquid. The liquid precursor hardens into solid or semi-solid SiOC. The solid or semi-solid SiOC is then pyrolyzed into ceramic SiOC, which is converted to SiC.
[0111] Silicon carbide generally does not have a liquid phase, but instead sublimes under vacuum at temperatures of about 1,700-1,800 °C. Figure 17 shows a chart of the partial pressure curves for SiC. Typically, in industrial and commercial applications, conditions are established such that sublimation occurs at temperatures of about 2,500 °C or higher. When silicon carbide sublimes, a vapor is formed that is typically composed of several different species of silicon and carbon. It was generally thought that temperature determined the ratio of these different components in the silicon-carbon vapor.
[0112] However, the present invention provides, among other things, the ability to preselect and control the ratios of different species present in the silicon carbon vapor, e.g., SiC, SiC, Si2C, and SiC2. Thus, in addition to temperature, the present invention allows control of the silicon carbon species in the vapor in and between the starting material (e.g., a puck of SiC) and the surfaces (where the silicon carbon vapor will be deposited and become a solid, e.g., a crystal, growing, e.g., into a boule). This silicon carbon vapor in the deposition process can be referred to as the "flux."
[0113] Preferred embodiments of the boule are single crystal and have only a single polytype, although embodiments of the boule having multiple polytypes, multiple crystals, and both are also contemplated herein.
[0114] For example, by controlling the amount of carbon present relative to the amount of silicon present in the polysilocarb derived SiC, or in the volume shapes used as starting materials, the amount of Si and C present in the flux can be predetermined and controlled. Furthermore, by varying in a controlled manner, for example, the porosity of the polysilocarb derived SiC, the volume shapes and the porosity of both, the flux amount, the rate of flux formation, and the species of silicon and carbon present in the flux can be predetermined and controlled.
[0115] For example, the amount of carbon present in the starting material or starting pack can be excess (more than stoichiometric, i.e., more than 1:1 silicon to carbon) or deficient (less than stoichiometric carbon). In this way, the amount of carbon in the starting material or in the volume shape, e.g., as a pack, can be set or established. This amount can be set, for example, by (I) using different binders to form the volume shape, (II) having layers in the SiC material with different amounts of carbon; (III) having zones in the SiC volume shape with different predetermined amounts of carbon; (IV) combinations and variations thereof, and by controlling the amount of carbon present in the starting material in a predetermined manner. Furthermore, by controlling and predetermining the ratio of carbon to silicon in the starting material, these ratios can be controlled and predetermined in the flux.
[0116] The present invention provides embodiments of methods and processes for growing a boule, e.g., forming a single crystal boule of SiC by deposition of SiC such that the face of the boule is very flat, e.g., has a limited amount of curvature or arc. The very flat profile of the boule is achieved primarily through the use of a preselected shape of the SiC puck placed in the deposition apparatus. The preselected shape is configured such that during the deposition process, the area of flux and the flow within that area remain constant throughout the boule growth process. In this manner, the rate and amount of SiC that deposits on the surface of the boule as it grows is consistent throughout the boule growth process. Thus, for example, when growing a 6 inch diameter boule, the flux flow area is 28.27 inches square and the flow rate and amount of SiC flowing through that area is consistent throughout that area during the growth of a 3 inch or 4 inch long boule. The shape of the puck directs the flux (e.g., "directional flux") during the process such that the flux flow remains uniform throughout the area immediately adjacent the face of the boule, even as the amount and location of SiC available for sublimation changes within the puck. Examples of geometries that provide directional flux are shown in Figures 4A-4F and 5A-5F.
[0117] In one embodiment, the flux is not maintained constant throughout the growth process. Thus, in this embodiment, the rate, distribution of the flux across the growth surface is managed, e.g., controlled in a predetermined manner, to provide a predetermined growth of the boule or region of the growth surface. For example, in later stages of growth, the flux is directed in a predetermined manner to compensate for non-uniformities that have occurred in the growth of the boule. In this example, regions that had a high flux in the early stages of growth will have a low flux in the later stages of growth. Similarly, regions that had low flux in the early stages of growth will have a high flux in the later stages of growth. In this way, the final boule growth surface minimizes the curvature, or maximizes the radius of curvature, of the boule surface.
[0118] In one embodiment, the use of controlled flux, and more preferably directional flux, can provide a 4 inch boule with a radius of curvature (i.e., the inverse of the curvature) of at least about 6 inches, at least about 6 inches, 8 inches, at least about 20 inches, at least about 60 inches, close to infinity (i.e., flat), and all values within these ranges of values. In one embodiment, a 6 inch boule can be provided with a radius of curvature (i.e., the inverse of the curvature) of a 6 inch boule, about 10 inches, at least about 15 inches, at least about 25 inches, at least about 60 inches, infinity (flat), and all values within these ranges of values. In one embodiment, the radius of curvature of the boule face has a radius of curvature of at least 2 times the length of the boule, at least 5 times the length of the boule, at least 10 times the length of the boule, and at least 25 times the length of the boule, or infinity (flat), and all values within these ranges of values. A boule 2100 is shown in FIG. 21. The boule 2100 has a length indicated by arrow 2102, and a width or diameter indicated by arrow 2103. Boule 2100 has a face (e.g., a growth face) 2101 with a curved surface 2101A that defines the radius of curvature of boule 2100. The radius of curvature of curved surface 2101A is indicated by dashed line 2104.
[0119] In one embodiment, the flux can be manipulated by pressure as well as temperature. At a particular growth temperature, growth can be slowed down by increasing the chamber pressure. The fastest rates are usually under "perfect" vacuum (e.g., with the vacuum pump on and the chamber pressure kept as low as possible). As an example, to grow a boule at 400 μm / hr, growth can be at full vacuum P1 at temperature T1, or at partial pressures of argon (P2>P1) ranging from a few mBar to tens of mBar at temperatures T2>T1. In this way, the flux and growth rate can be "tuned".
[0120] In one embodiment, polymer derived SiC provides better polytype stability within the boule due to a more consistent flux composition over time. This embodiment, controlled polytype stability, is valuable and important to boule manufacturers. Polytype shift mid-growth means that only a portion of the boule is the original polytype which can adversely affect electronic properties that typically impact device performance of the chip.
[0121] The present invention provides the ability to "tune" the flux through the use of polymer derived SiC and predefined pack geometries, allowing less efficient deposition equipment to produce boules with substantially improved quality, quantity, production rate, combinations and variations thereof. In this way, the performance of lower quality deposition equipment can be significantly improved, even to the point of being comparable to or even surpassing that of higher quality deposition equipment. In this way, for example, the ability to tune current geometries and fluxes gives existing deposition equipment, without mechanical modifications, the ability to produce boules with 10% fewer defects, 20% fewer defects, 50% fewer defects, 100% fewer defects, 2x, 3x, 4x or more production rates, and flatter surfaces, i.e., at least 2x, at least 3x, at least 4x flatness, as well as all within these ranges, combinations and variations of these improvements, i.e., fewer defects, improved rate, improved flatness. Tuning the flux allows deposition equipment, without mechanical modifications, to have 1.5x, 2x, 3x or more boule production capacity with one or more of the improved quality features described herein.
[0122] FIG. 18 shows a schematic cross-sectional view of an apparatus for growing SiC crystals, crystal structures and boules. The deposition apparatus 1800 is a vessel having side walls 1808, a bottom or bottom wall 1809, and a top or top wall 1810. The walls 1808, 1809, 1810 have ports 1806, 1807, 1805, which may be openings, nozzles that control or allow the flow of gases into and out of the device 1800. Associated with the device 1800 is a heating element 1804. The heating element can be configured and operated to provide a single temperature zone or multiple temperatures within the apparatus 1800. Inside the apparatus 1800 is a puck 1801 made of SiC particles formed into a volumetric shape.
[0123] The puck 1801 can have a predetermined porosity and density. The SiC particles can have a predetermined porosity and density. The SiC particles are preferably held together by a binder. The puck 1801 can be carbon rich, carbon poor, or stoichiometric. The puck 1801 can have carbon rich, carbon deficient, or stoichiometric zones or layers. Preferably, the SiC particles are SiC from a SiOC polymer. Non-polymer derived SiO can also be used as part or all of the puck. The puck 1801 has a height indicated by arrow 1826 and a diameter or cross section indicated by 1820. The puck 1801 has a top or upper surface 1823 and a bottom surface 1824. In this embodiment, the puck 1801 is shown as a flat top and bottom cylinder, but it should be understood that any shape of volumetric shape can be used in the device 1800.
[0124] On top 1810 of device 1800 is a seed crystal 1802 having surface 1802a. Seed crystal 1802 has a cross section or diameter 1822 and a height 1823. In some embodiments, the seed crystal is mounted on a movable platform 1803 such that the distance between surface 1802a and surface 1823 can be adjusted.
[0125] The diameter 1820 of the puck 1801 may be larger than, smaller than, or the same as the diameter 1822 of the seed crystal 1802 .
[0126] In operation, heating element 1804 raises the temperature of puck 1801 to a point where SiC sublimes. This sublimation forms a gas containing various species of silicon and carbon. This gas, or flux, resides in region 1850 between surfaces 1802a and 1823. Depending on porosity or other factors, flux may also reside within puck 1801. The flux rises through region 1850 within apparatus 1800, depositing SiC on surface 1802a. Surface 1802a must be maintained at a temperature low enough to deposit gaseous silicon carbon species on the surface that will form SiC crystals. In this manner, seed crystal 1802 is grown into a boule by successive additions of SiC grown in a polytype-matched orientation on its surface. Thus, unless accommodated by device 1803 (shown in a fully retracted position), during boule growth, surface 1803 will grow toward bottom 1809, thus decreasing the distance between surface 1802a and bottom 1809. A form of flux can be used to create a predetermined temperature differential within the puck during the deposition process. This predetermined temperature differential can address, reduce, or eliminate the deleterious effects of passivation, where species accumulate in the puck during the process to reduce or prevent the formation of SiC vapor.
[0127] It is theorized that the process of sublimation and deposition occurs inside the volume shape of the raw material itself and follows the thermal gradient of the raw material that occurs naturally or which thermal gradient may be determined by the shape of the pack. In one embodiment, the binder preferably remains present and maintains the shape and integrity of the pack during the sublimation temperature and therefore does not sublimate below the sublimation temperature of SiC. This temperature gradient is usually upward from the outside to the inside. It is theorized that the material continuously sublimes and redeposits on adjacent particles, thus undergoing reflexing of the SiC species or "fractional distillation" or "fractional sublimation" of the solids.
[0128] Theoretically, in one embodiment, the volume geometry and its predetermined gradient can trap some of the heavier impurities in the puck at the back of the bottom of the growth chamber, while the lighter elements can be sublimated with the Si-C vapor and carried to the seed. This can theoretically allow dopants or other additives to be released at predetermined times in the process, mitigating the potentially adverse effects of impurities. It should be understood that preferably, ultra-pure materials are used in the puck.
[0129] In embodiments, the puck provides a more consistent flux formation rate for a given temperature. The shape can be tailored to provide a more uniform temperature throughout the shape, and can allow a higher volume fraction of the shape to sublimate at one time, driving a higher flux rate at the seed / vapor interface at a particular temperature than a standard deposit of powder, i.e., a cylinder. Thus, growth of polytypes requiring a lower temperature growth process is not limited to slower growth rates as a result.
[0130] Sublimation rate is measured in grams / hour. Flux is measured in grams / cm 2-hr (i.e., the rate of material passing through the area). The area of interest is therefore the flux area, which corresponds to the instantaneous surface area of the boule growth surface, e.g., the face of the boule on which SiC is being deposited. Typically, the flux area and the area of the boule face are approximately the same, and these areas are usually slightly smaller than the cross-sectional area of the deposition equipment growth chamber.
[0131] For purposes of calculation and this analysis, the cross-sectional area of the growth chamber is assumed to be the same as the area of the flux and the area of the boule face to facilitate calculations. Thus, the growth rate of the boule (mm / hr) is calculated by multiplying the area of the boule (cm 2 ) can be equivalent to the steam flow rate throughout the growth (mm / hr >= g / hr; fully dense SiC has a density of 3.21 g / cc). In-situ measurements can be done via X-ray imaging or X-ray computed tomography (CT). Otherwise, the average growth rate can be determined by weighing the boule before and after growth.
[0132] Typical commercial growth rates are in the range of 200-500 mm / hr. The present process and volumetric shape embodiments far exceed these existing ones while providing boules of comparable and superior quality. For example, embodiments of the present invention can have growth rates of about 550 to about 1,1000 mm / hr, about 800 to about 1,000 mm / hr, about 900 to about 1,100 mm / hr, about 700, about 800 mm / hr, 900 mm / hr, 1,000 mm / hr, 1,100 mm / hr at high temperatures and low pressures. As with all rates within these ranges, higher rates are contemplated and slower rates may also be used.
[0133] In general, the growth rate depends on 1) the temperature and 2) the supply gas pressure (AR, N 2The growth rate is driven by the gas pressure (e.g., 1000 MPa, 1000 MPa, 1000 MPa, 15 ...
[0134] With reference to FIG. 19, it can be seen that embodiments of the present invention do not exhibit passivation (surface passivation). They are not self-limiting and are not passivated. These embodiments provide significant improvements and advantages over existing sources of SiC starting material in vapor deposition processes. These existing SiC sources have a self-limiting effect, where the rate of flux generation decreases over time as the surface effects of the starting material limit or inhibit sublimation. This self-limiting effect is commonly known as passivation, but is also referred to as source depletion, graphitization, or carbonization.
[0135] Thus, in embodiments of a volumetric shape (e.g., a puck) that is provided with a constant temperature, a constant rate of flux generation can be maintained throughout the boule growing operation, including boules of about 4 inches to about 10 inches diameter, about 6 inches to about 8 inches diameter, about 4 inches diameter, about 6 inches diameter, about 8 inches diameter, and above and below, as well as all diameters within these ranges. In embodiments of a volumetric shape that is provided with a constant temperature throughout the boule growing process, a rate of flux generation can be maintained throughout the boule growing, and thus the growth rate of the boule at a constant rate, i.e., a rate rate change of less than about 0.001%, less than 0.01%, less than about 1%, less than about 5%, less than about 20%, about 0.001% to about 15%, about 0.01% to about 5%, and combinations and variations thereof, and constant growth rates within these values. In embodiments, at a constant temperature, the rate of flux formation remains at: about 99.999% to about 60% of its maximum rate; about 99% to about 95% of its maximum rate. From about 99.99% to about 80% of the maximum speed. From about 99% to about 70% of the maximum speed. From about 95% to about 70% of the maximum speed. From about 99% to about 95% of the maximum speed, and combinations and variations of these while the boolean is growing, and all values within these percentage ranges.
[0136] The embodiments have an inherent bulk density. In one embodiment, the volumetric shapes, e.g., pucks, are made in a molding process, so the powder can be compressed to very high bulk densities, up to 2.0 g / cc (2.0 / 3.21 = 62% packing or 38% porosity). The resulting shape maintains the same high surface area as the starting material particles, and allows for more weight of material to occupy the bottom of the growth chamber. In this way, taller boules can be grown from denser source material. Also, more feedstock that remains active throughout the growth process allows for longer growth times, longer and wider boules. These benefits are regardless of the final shape of the growth interface. This also allows for extended growth cycles to further grow larger boules.
[0137] In this manner, capacity utilization of the growth portion of the cycle of the deposition process can be maximized. Thus, embodiments of the present invention provide the ability to significantly increase capacity utilization of the growth cycle of existing deposition equipment. Typically, existing deposition equipment requires ~10-30 hours of heat-up time (which is not part of the growth cycle) and ~30-50 hours of cool-down time (which is not part of the growth). These non-growth cycle times increase with larger boule sizes (where thermal shock to the chamber and boule cannot be tolerated or may be damaged). If the growth cycle (i.e., the time during the heat cycle during which sublimation and deposition to grow the boule is occurring) is extended by 10-20 hours, boule growth can be increased by 400 μm / hr. This significantly increases the yield of wafers per boule growth cycle, reducing the cost of consumables and ultimately the manufacturing cost per wafer. Thus, embodiments of the present invention can increase capacity utilization of the growth period of the furnace.
[0138] Thus, in embodiments, deposition apparatus growth cycles for the same diameter boule can be increased by about 10% to about 100%, about 10% to about 60%, about 20% to about 60%, about 33% to about 70%, at least about 30%, at least about 50%, at least about 70%, and all values within these percentage ranges using the present polymer-derived SiC and volumetric feature embodiments compared to using currently available SiC source materials. In embodiments, the polymer-derived SiC and volumetric shapes of the present invention can be used to increase the number of wafers of the same thickness and diameter ultimately obtained from a single growth cycle (growing a boule and then cutting into wafers of the same thickness) by about 10% to about 500%, about 100% to about 300%, about 10% to about 70%, about 30% to about 70%, at least about 20%, at least about 50%, at least about 100%, at least about 200%, at least 2 wafers, at least 10 wafers, at least 20 wafers, at least 100 wafers, at least 1,000 wafers, about 2 to 100 wafers, about 10 to 100 wafers, about 50 to 200 wafers, about 100 to 500 wafers, etc., and all values within these ranges, compared to using currently available SiC feedstock. The present boule embodiments also provide the ability to obtain more wafers from a single growth cycle because they have substantially fewer defects than boules grown from conventional SiC source materials. This increased wafer production, improved efficiency of boule growth, and improved boule quality can further have the effect of increasing device production from a single growth cycle. Thus, the number of devices can be increased by at least about 100, at least about 200, at least about 1,000, at least about 10,000, at least about 100,000 or more, from about 100 to about 10,000, from about 1,000 to about 30,000, from about 500 to about 20,000, and from about 20,000 to about 50,000, and all values within these ranges.
[0139] Embodiments provide the ability to achieve shape control over predetermined shapes, many of which are believed to be unknown and most cannot be obtained using existing starting materials. The shape of the volumetric shape, e.g., puck, that is placed in the deposition apparatus as source material for boule growth drives or actively influences many parameters of the growth process, resulting in larger boules, higher quality boules, higher quality wafers, and more wafers compared to conventional feedstock. These improved growth parameters include: a radial temperature gradient in the source; an increased axial temperature gradient in the source; an increased sublimation area; reduced flux restriction; a higher internal source temperature to provide more uniform sublimation throughout the source material; a faster flux and a guided flux path through the source material (directing the vapor to the desired location (center or edge or both, providing a particularly flat boule growth surface). The flux can be directed to the edges of the boule during the later stages of growth so that the edges can grow as fast as the center while the source is more completely consumed near the edges. Thus, the final shape provides a boule with a flat surface rather than the typical convex boule obtained using current source materials, which wastes boule material that cannot be used to produce wafers, thus significantly increasing the amount of boule that can be used to make wafers.
[0140] In addition to the above, additional benefits derived from the ability to have a predetermined shape of the starting material include: allowing radiative heating of the center of the growth surface through line of sight to the crucible bottom, reducing radial temperature gradients on the seed crystal, allowing for the growth of even larger boules (8", 10" and above) and also reducing cooling cycles to reduce stress on the crystal and prevent cracking; improving polytype stability and reducing line defects / dislocations due to more uniform boule temperature and resulting reduced thermal stress on the boule compared to using existing starting material in the same deposition equipment; more complete utilization of source material as no starting material can be pre-selected or determined to not be fully sublimated by the end of the process; reducing waste raw material and improving raw material to boule yield and cost efficiency by sublimating large volumes of raw material to form the boule.
[0141] The center of the boule at the growth front is typically cooler than the edges, making it more of a "sink" for material deposition (a source to sink the vapor flux). So, in theory, if there is a line of sight (hole) from bottom to top through the source material, radiation from the bottom of the crucible will reach the center of the boule face, warming it up a bit (a matter of tens of degrees Celsius), making the center less of a "sink," making the temperature across the seed more uniform, creating a more uniform flux at all positions along the crystal, and allowing for a flatter boule. Additionally, it is theorized that this open line of sight geometry embodiment allows material in the center of the source material to be more effectively sublimated into the boule. This center is the coolest part, and therefore is typically the last place to sublimate, and growth will cease before the source material is depleted. Examples of open line of sight geometry puck embodiments are shown in Figures 9 and 10.
[0142] The embodiments provide a distribution of density of the source material throughout the volumetric shape used as the starting material in the deposition apparatus. This predetermined density distribution provides several advantages and improvements over existing source materials, such as improved heat transfer to specific parts, predetermined and controlled heat transfer to specific parts or regions of the shape, such as limited heat transfer so that the source is consumed uniformly throughout, and controlled and preferably uniform heat transfer during the growth cycle. The sublimation composition (i.e., the composition of the vapor formed from the sublimation of the starting material, such as the flux composition) can also have a more sustained or uniform composition throughout the cycle or a more amplified composition at the beginning of growth, providing, among other things, better polytype stability due to the stable composition.
[0143] The embodiments provide for layers, zones, regions with a distribution of different powder stoichiometries throughout the shape, e.g., different types of powder starting materials, different binders, and combinations and variations thereof. This predetermined distribution of different stoichiometries provides several advantages, including customization of the sublimation composition, which results in less change in composition from the beginning to the end of the growth cycle as raw materials are consumed externally. This predetermined distribution of different stoichiometries can also increase the stability of the polytype due to the consistent composition of the vapor.
[0144] The embodiments provide for adjusted stoichiometry of the raw materials or starting raw powders, i.e. adjusted stoichiometry of the volume shape binder, additives to the volume shapes, additives to the starting material powders, and combinations and variations thereof. For example, using up to 20% liquid phase binder and particles can shift the stoichiometry from, for example, 1.5:1 SiC to 1:1.5 SiC and values within these ratios. Larger and smaller shifts are contemplated. The stoichiometry is maintained using PDC precursors and water, or evaporated solvents, or non-Si or non-C compounds (e.g., boric acid, alumina, aluminum nitride, aluminum nitrate, calcium nitrate, sodium phosphate). The stoichiometry is shifted to C-rich using LDPE, carbon black, graphite powder, boron carbide, PAN, wax, polylactic acid, cellulose, sucrose / sugar, sodium bicarbonate, starch, etc. The stoichiometry is shifted to Si-rich using Si powder, starting Si-rich SiC, silica, soda-lime glass, borosilicate glass, and silicon nitride.
[0145] Silicon- or carbon-rich stoichiometric species have higher silicon or carbon content, respectively, in the vapor flow at the start of growth, which can affect the polytype stability of the growth. Thus, for example, having a source stoichiometry that provides a carbon-rich vapor phase can enhance the stability of the 4H polytype. Nitrogen doping in the volume doping, gas flow, or both can similarly enhance the stability of the 4H polytype. Similarly, a growth temperature between 2,100 and 2,500 °C can enhance the stability of the 4H polytype.
[0146] This ability to tune the powder stoichiometry can be combined with the ability to tune the geometric location of the silicon-rich phase. In this way, the location of the silicon-rich phase can allow the "graphitization" phenomenon of depleted SiC to react in situ to form additional SiC for sublimation. Alternatively, the Si-rich regions can offset the reduction in the Si content of the gas phase during later stages of growth. This allows for a more consistent flux of silicon-carbon species throughout the growth period, especially during the later stages of growth.
[0147] In general, the process to obtain SiC involves the process from liquid precursor formulation to cured material, the cured material to pyrolyzed SiOC material and then converted to SiC material (alpha, beta or both). During these processes (curing, pyrolysis, conversion), some of the different components are lost, usually C and O. Si can also be lost, but it is desirable that the process and precursors are such that the loss of Si is minimized. For example, excess C incorporated in the precursor or C generated from an external source, for example in an oven, promotes the production of CO over SiO, resulting in less Si loss. The greater the degree of crosslinking that occurs in the cured material, the lower the Si loss during pyrolysis and conversion and the higher the yield of SiC.
[0148] Processes, formulations, and systems for producing high and ultra-high purity SiC and SiOC are disclosed and taught in U.S. Patent Publication No. 2016 / 0207782, which is incorporated herein by reference.
[0149] In an embodiment, the hardened SiOC can be a volume shape, e.g., puck, pill, pellet, plate, bead or disk, that is directly converted to friable SiC chunks without the need for intermediate processing steps and with minimal grinding. In one embodiment, the hardened SiOC is ground into granular SiOC, which is then converted to granular SiC, which is then formed into a volume shape using a binder. In one embodiment, the (hardened or pyrolyzed) SiOC is formed into SiC particles, which are then, e.g., compressed, into a volume shape, i.e., a SiC chunk. Preferably, the size and size distribution of the SiC particles is predetermined, and no further grinding is required. In an embodiment, these particles can be ground into smaller, more uniform, or both granules, if necessary. The granules can then be formed, e.g., pressed, into a volume shape, i.e., a SiC chunk. In these and other embodiments, to produce high and ultra-high purity SiC, it is preferable that all components of the system are free of materials that would be considered impurities in the subsequent use or process of the SiC. Alternatively, it may be preferable to shield, package, or take other mitigation steps to these components to prevent impurities from being introduced into the process.
[0150] FIG. 16 shows a schematic perspective flow diagram of an embodiment of a system and method for making SiC derived volume shapes from SiOC, preferably of high purity (e.g., 3, 4, 5 NINES and higher). The lines, valves, and internal surfaces of the system, including precursors and other materials, are made of or coated with materials that will not contaminate the SiOC, derived SiC, and SiC volume shapes. Storage tanks 150a, 150b hold liquid polysilocarbon precursors. In this embodiment, one or both of the precursors can be removed through distillation apparatus 151a and distillation apparatus 151b to remove impurities from the liquid precursors. The liquid precursors are then transferred to a mixing vessel 152, where they are mixed to form a precursor batch and catalyzed. In a clean room environment 157a, the precursor batch is packaged in a vessel 153 for placement in a furnace 154. The furnace 154 has a sweep gas inlet 161 and an off-gas removal line 162. The packaged and cured material is then transported under clean room conditions to several pyrolysis furnaces 155a, 155b, 155c where it transitions from SiOC to SiC. The furnaces have sweep gas inlet lines 158a, 158b, 158c, respectively, and two off-gas removal lines 159a and 160a, 159b and 160b, 159c and 160c, respectively. The off-gas can be treated, cleaned, and starting materials recovered in an off-gas treatment assembly 163, which has an inlet line 164 that collects off-gas from various units in the system.
[0151] The resulting SiC is then transferred to a volume shape forming area 190, preferably under clean room conditions. In area 190, the SiC is provided to a mixing vessel 172 having a mixing device 173 (e.g., blades, paddles, agitators, etc.). Binder from a binder tank 170 is added to the vessel 172 via line 171. In the mixing vessel 172, the SiC is mixed with the binder to form a slurry or blend. The consistency of the slurry should be such as to facilitate the subsequent pelletizing operation. The SiC-binder slurry is then transferred to a forming device 175, where the slurry is formed into volume shapes, e.g., pellets, disks, blocks, etc., and fed to an oven 177, where the binder hardens to give the volume the desired strength. The hardened volume shapes are then transferred to a packaging device 180, where they are packaged. Preferably, these operations are carried out under clean room conditions, and more preferably, the operations are carried out in separate clean rooms, or areas 190a, 190b, 190c of the clean room.
[0152] Preferably, in producing SiC and materials for use in the production of SiC, in a preferred embodiment, the polysilocarb precursors are mixed in clean air at about 1 atmosphere pressure.
[0153] Preferably, in the manufacture of SiC and materials for use in the manufacture of SiC, curing is carried out at temperatures ranging from about 20° C. to about 150° C., from about 75° C. to about 125° C., and from about 80° C. to about 90° C., combinations of these temperatures, and all values within these temperature ranges. Curing is preferably carried out for a period of time that results in a hard, cured material. Curing can be carried out in air or an inert atmosphere, and preferably, curing is carried out in an argon atmosphere at ambient pressure. Most preferably, for high purity materials, the furnace, vessel, handling equipment, and other components of the curing apparatus are clean and essentially free of impurities or contaminants to the material being cured.
[0154] Preferably, in the production of SiC and materials for use in the production of SiC, pyrolysis is carried out at temperatures ranging from about 800°C to about 1300°C, from about 900°C to about 1200°C, from about 950°C to 1150°C, and all values within these temperature ranges. Pyrolysis is preferably carried out for a period of time that results in complete pyrolysis of the preform. Preferably, pyrolysis is carried out in an inert gas, such as argon, more preferably in a flow of argon gas at atmospheric pressure or at atmospheric pressure. The gas can flow at about 1,200cc / min to about 200cc / min, about 800cc / min to about 400cc / min, about 500cc / min, and all values within these flow rates. Preferably, initial evacuation of the process furnace is completed to a reduced pressure of at least less than 1E-3 Torr and repressurized with an inert gas, such as argon, to greater than 100 Torr. More preferably, evacuation is carried out to a pressure of less than 1E-5 Torr before repressurizing with the inert gas. The evacuation process can be completed anywhere from 0 to 4 or more times. Most preferably, for high purity materials, the furnace, vessel, handling equipment, and other components of the curing apparatus are clean and essentially free of, and unable to produce, elements or materials that would be considered impurities or contaminants.
[0155] Pyrolysis can be carried out in any heating device that maintains the required temperature and environmental control. Thus, for example, pyrolysis can be carried out in pressure furnaces, box furnaces, tube furnaces, crystal growth furnaces, graphite box furnaces, arc melting furnaces, induction furnaces, kilns, MoSi2 heating element furnaces, carbon furnaces, vacuum furnaces, gas fired furnaces, electric furnaces, direct heating, indirect heating, fluidized bed, RF furnaces, kilns, tunnel kilns, box kilns, shuttle kilns, coking equipment, lasers, microwaves, other electromagnetic radiation, and combinations and variations of these and other heating devices.
[0156] In embodiments where low N and O levels are required, it is preferred to achieve a vacuum, preferably 10E-6 Torr using a turbo pump, and backfill with an inert gas. This purging process can be done one or more times to achieve low levels. A constant flow of "sweep" gas serves to purge the furnace during generation of volatiles.
[0157] Preferably, in the production of SiC, the ceramic SiOC is converted to SiC in a subsequent or continuing pyrolysis or conversion step. The conversion step from SiOC may be part of the pyrolysis of the SiOC preform, e.g., continuous, or may be a completely separate step in time, place, and both. Depending on the type of SiC required, conventional procedures can be carried out at about 1,200°C to about 2,550°C, about 1,300°C to 1,700°C, and all values within these temperature ranges. Generally, temperatures from about 1,600°C to 1,900°C promote the formation of the beta form over time. Temperatures above 1,900°C promote the formation of the alpha form over time. Preferably, the conversion is carried out in an inert gas, e.g., argon, more preferably in a flow of argon gas at or near atmospheric pressure. The gas may flow at about 600 cc / min to about 10 cc / min, about 300 cc / min to about 50 cc / min, and about 80 cc / min to about 40 cc / min and values within these flow ranges. Most preferably, for high purity materials, the furnace, vessel, handling equipment, and other components of the curing apparatus are clean and essentially free of and will not produce elements or materials that would be considered impurities or contaminants in the SiC.
[0158] The subsequent yield of SiC from SiOC is generally about 10% to 50%, typically 30% to 40%, but can range higher and lower, as well as all values within these percentages.
[0159] Most preferably, when producing high purity SiC, activities related to material production, curing, pyrolysis, and conversion are carried out under cleanroom conditions, e.g., ISO 14644-1 cleanroom standards of at least ISO 5, at least ISO 4, at least ISO 3, at least ISO 2, and at least ISO 1. In one embodiment, material handling steps are performed in a cleanroom of at least ISO 5, while less clean areas (ISO>5) are used for the pyrolysis and conversion steps.
[0160] The volumetric shapes of SiC or SiOC and ultra-pure SiC or SiOC can be any given volumetric shape, including, for example, spheres, pucks, pellets, rings, lenses, disks, panels, cones, frustoconical shapes, squares, rectangles, trusses, angles, channels, hollow enclosed chambers, hollow spheres, blocks, sheets, coatings, films, skins, particulates, beams, rods, angles, slabs, columns, fibers, staple fibers, tubes, cups, pipes, and combinations of these and other complex shapes.
[0161] When making volume shapes, the amount of binder added to the SiC can vary from a light coating of the SiC particles to an amount sufficient to form a slurry-like paste. Thus, depending on the requirements of the molding equipment, the strength requirements of the volume shape, and the binder itself, about 0.1% to about 65%, about 0.1% to about 45%, about 0.5% to about 40%, about 20% to about 40%, about 1% to about 15%, and about 2% to about 7%, about 1% or more, about 2% or more, and about 3% or more and all amounts within these percentage ranges of binder can be added to the SiC to form a slurry or blend. Depending on the amount of binder lost during curing, volume shapes can include about 0.05% to about 25%, about 0.75% to about 12%, 1% to about 5%, about 1% or more, about 2% or more, about 4% or more, about 6% or more and all amounts within these percentage ranges of cured binder.
[0162] The size of the SiC granules mixed with the binder to form the volume shape can be from about 0.1 μm (microns) to about 100 μm, about 0.5 μm to about 50 μm, about 0.3 μm to about 20 μm, about 0.3 μm to about 10 μm, and larger and smaller sizes, combinations of different sizes, and all values within these size ranges. Thus, the granules can have a primary particle diameter of about 0.1 μm to about 20.0 μm, about 0.5 μm to about 10.0 μm, about 0.5 μm to about 2.0 μm, about 0.5 μm to about 1.0 μm, about 1 μm to about 5 μm, about 1 μm, about 2 μm, about 3 μm, and larger and smaller sizes and all values within these size ranges. 50 It may have a size.
[0163] The binder can be any binder used to hold the SiC in a given shape during processing, curing, and subsequent use of the volume shape. Binder embodiments can be preferably oxygen-free. Binder embodiments can be preferably composed of materials having only carbon and hydrogen. Binder embodiments can be made from materials having oxygen. Binder embodiments can be any sintering aid used in sintering SiC. Binder embodiments can be fused silica. Binder embodiments can be polysilocarb precursor materials, including all of the liquid precursors described herein. Combinations and variations of these and other materials may also be used as binders.
[0164] The binder can be cured to the extent necessary under conditions used to cure the polysiloxane precursor or under conditions necessary to convert the binder into a material that is hard (e.g., tough) enough to hold the volume shape. Thus, in some cases, curing, hardening, forming, or setting up must be done based on the properties of the binder. Consideration must be given to preventing the curing or hardening or setting up of the binder to introduce impurities or other undesirable materials into the volume shape.
[0165] Examples of oxygen-free binder embodiments include polyethylene, silicon metal, hydrocarbon wax, polystyrene, and polypropylene, as well as combinations and variations thereof.
[0166] Examples of binder embodiments that contain only carbon and hydrogen include polyethylene, hydrocarbon waxes, carbon or graphite powder, carbon black, HDPE, LDPE, UHDPE, and PP, and combinations and variations thereof.
[0167] Examples of oxygen-containing binder embodiments include boric acid, boron oxide, silicon dioxide, polyhydric alcohols, polylactic acid, cellulosic materials, sugars and sugars, polyesters, epoxies, siloxanes, silicates, silanes, silsesquioxanes, acetates such as ethyl vinyl acetate (EVA), polyacrylates such as PMMA, polymer-derived ceramic precursors, and combinations and variations thereof.
[0168] Examples of embodiments of binders that are sintering aids include ceramic precursors derived from silicon, boron oxide, boric acid, boron carbide, silicon and carbon powders, silica, silicates and polymers, and combinations and variations thereof.
[0169] For pure and ultra-pure SiC materials for use in applications such as growing boules and for manufacturing wafers, the binder material is preferably free of all materials that would be considered contaminants. Thus, in embodiments, the binder material is at least 5 nines, at least 6 nines, at least 7 nines, and at least 8 nines pure, e.g., free of materials that would be considered contaminants.
[0170] Preferably, the use of the binder does not add any detectable amount of contaminants to the SiC or SiOC. In one embodiment, the binder also maintains the proper stoichiometry of the SiC to maintain a silicon to carbon atom ratio of approximately 1:1 after processing. In one embodiment, the binder has a predetermined SiC ratio that is carbon rich, carbon deficient, or stoichiometric to provide a volumetric shape having a predetermined SiC ratio.
[0171] For pure and ultra-pure SiC applications and materials, the binder may preferably be cosmetic grade, electronics grade, and surgical grade materials.
[0172] Binder embodiments include both catalyzed and non-catalyzed precursor formulations as disclosed and taught in U.S. Patent Nos. 9,499,677, 9,481,781 and U.S. Patent Publication Nos. 2014 / 0274658, 2014 / 0323364, 2015 / 0175750, 2016 / 0207782, 2016 / 0280607, 2017 / 0050337, the entire disclosures of each of which are incorporated herein by reference. Methods of curing these binders are disclosed and taught in these patents and published applications, the entire disclosures of each of which are incorporated herein by reference.
[0173] In a preferred embodiment, the SiC volume shapes are made using polymer-derived, preferably polysilocarb polymer-derived SiC (e.g., as taught and disclosed in U.S. Publication No. 2016 / 0207782, incorporated herein by reference) and a polysilocarb binder. In one embodiment, the SiC is from a conventional source. This embodiment is less preferred because conventional SiC has a different structure, e.g., morphology and surface properties, and is believed to perform less well than polymer-derived SiC in applications such as deposition. In an embodiment, the volume shapes are a mixture of polymer-derived SiC and conventional SiC.
[0174] In one embodiment, a binder is used to provide electrical conductivity to the tablet, bead or volume shape. Thus, the binder can be carbon, silicon, or can be decomposed in situ into conductive species such as carbon. Examples include polysaccharides, PE, hydrocarbon oils, waxes, etc., or polysilocarb formulations with a high carbon excess. A stoichiometric ratio of SiC can be achieved, and instead a C-SiC composite can be formed in situ, or carbon and silicon can be added. In this way, the volume shape, such as a disk, puck, pellet, bead, tablet, pill, etc., has a resistivity of less than 10,000 ohm-cm at 20°C, less than 8,000 ohm (ohm)-cm at 20°C, less than 5,000 ohm-cm at 20°C, less than 2,000 ohm-cm at 20°C, and all values within these resistivity ranges.
[0175] Generally, in one embodiment, the binder material is completely volatilized below 700° C., completely volatilized below 600° C., completely volatilized below 500° C., and all values within these temperature ranges. When using different types of PDC as the binder material, the volatilization range can vary, so the volatilization temperature range of the binder can be from about 900° C. to about 300° C., and all values within these temperature ranges. It is also preferred that the volatile components of the binder do not deposit on or otherwise foul or contaminate the internal components of the equipment being used to make structures from SiC, such as deposition equipment.
[0176] Preferred embodiments of binder materials for use with ultra-pure SiC to form volume shapes, such as tablets, discs, pucks, pills, pellets, beads, etc., having a purity (for volume shapes) of at least about 5 9's with a resistivity of less than 8,000 ohm-cm at 20° C. are silicon metal, carbon powder, hydrocarbon wax, pure polyethylene, and distillable compounds containing primarily silicon, carbon, and hydrogen, polymer-derived ceramic precursors, and combinations and variations thereof.
[0177] Equipment and processes for forming volumetric shapes include, for example, cold pressing, cold isostatic pressing, hot pressing, hot isostatic pressing, extrusion, die casting, and molding processes, as well as combinations and variations thereof.
[0178] In embodiments utilizing directional flux, reflux, fractional distillation or fractional sublimation, and other embodiments where the shape retains structural integrity during most, preferably the entire, growth cycle, the binder must be one that does not sublime or lose its ability to maintain the structural integrity of the volume shape. Examples of these types of binders include PDC precursors as binders. A preferred embodiment to maintain the structural integrity of the volume shape, for example to function as a reflux structure, would be 10%-15% by weight of pure PDC precursor material.
[0179] The ability to start with a liquid material, e.g., a precursor batch, that has essentially all the building blocks, e.g., Si and C, needed to make SiC provides significant advantages in controlling impurities, contamination, and making high purity SiOC that can be converted to high purity SiC or made directly in a single combined process or step. Thus. Also, based in part on the performance of the present polymer-derived SiC in deposition equipment and growth boules, it is theorized that polymer-derived SiC is significantly different from non-polymer-derived SiC. Thus, synergies in boule growth and purity, wafer yield, device yield arise from the individual advantages of the present invention, such as bulk density, grain size, SiC phase (beta vs. alpha), stoichiometry, oxygen content (very low to none, lack of oxide layer), high purity, and ultra-high purity.
[0180] Thus, embodiments of the present invention provide for the use of SiOC and SiOC volume shapes of purity of at least about 99.9% (3-nines), at least about 99.99% (4-nines), at least about 99.999% (5-nines), and at least about 99.9999% (6-nines), and at least about 99.99999% (7-nines) or more, and all values within these purity ranges. Similarly, embodiments of the present invention provide for the use of SiC and SiC volume shapes of purity of at least about 99.9% (3-nines), at least about 99.99% (4-nines), at least about 99.999% (5-nines), and at least about 99.9999% (6-nines), and at least about 99.99999% (7-nines) or more, and all values within these purity ranges. These purity values are based on the amount of SiOC or SiC, as the case may be, relative to all materials present or contained in a particular sample of the SiOC or SiC product. As used herein, SiOC or SiC products refer to powdered SiOC or SiC, as well as volumetric forms of these materials. With appropriate binder selection, the SiC and SiOC volumetric forms embodiments have the same purity levels.
[0181] Lower purity levels in volumetric shapes may also be acceptable if they do not adversely affect the use of SiC and SiOC in the intended manufacturing process or end application, and if the contaminants are acted upon (or removed) without adversely affecting the final product manufactured from the SiC and SiOC starting materials. Thus, for example, a pure disk of 4-nines SiC with a purity of 7-nines SiC may be acceptable where the binder that reduces the overall purity of the disk has been removed before reaching 700°C in the boule formation vapor deposition process. Additionally, impurities that are too heavy (high AMU) are mitigated as they may be trapped within the pack.
[0182] In embodiments of the invention, high purity SiC volume shapes are provided with very low detection limits and low detectable amounts that would cause significant problems in the final product or be considered impurities in the subsequent processing and manufacture of items such as boules, wafers, electronic components, optical components, and other SiC-based intermediate and final products.
[0183] Thus, the high purity SiC derived from polymers, and particularly the high purity SiOC derived from polysilocarb, as well as the high purity SiC to which SiOC is converted, have a purity of at least about 99.9%, at least about 99.99%, at least about 99.999%, at least about 99.9999%, at least about 99.99999% or more. It is further noted that embodiments of the present invention include polymer derived SiC and SiOC at any purity level, including lower levels of purity such as 99.0%, 95%, 90% or less. It is believed that these lower, e.g., non-high purity, embodiments have and will find substantial uses and applications. Similarly, it is believed that the high purity SiC embodiments will find uses, applications, and provide new and surprising benefits in applications that were previously limited to materials other than Si or SiC. The volumetric shape embodiments of SiC with appropriate binder selection have the same purity levels.
[0184] Embodiments of the invention include the use of high purity SiC in making wafers for use in electronics and semiconductor applications. High purity SiC is required in both the deposition equipment and the process of making boules and wafers for subsequent use. In particular, as shown in Table 1, embodiments of high purity SiC may be preferred having low levels of all elements in Table 1 that are considered impurities in certain deposition equipment, electronics applications, and semiconductor applications. Thus, embodiments of SiC particles and volumetric shapes can be free of impurities, substantially free of impurities, and can include amounts that do not exceed the amounts and combinations of amounts shown in Table 1.
[0185] Table 1 JPEG2025024179000002.jpg185158
[0186] In one embodiment, Pr may be considered an impurity in some applications, and if so considered, the limits and amounts in Table 1 may be applicable to Pr.
[0187] Unless otherwise stated, as used herein, when referring to purity levels, high purity, % purity, % impurities, and similar terms, excess carbon, i.e., beyond stoichiometric SiC, is not included, referenced, considered, or used in calculations or characterization of the material. In some applications, excess carbon may have little or no effect on the application or product and is therefore not considered an impurity. In other applications, excess carbon may be beneficial. For example, carbon acts as a sintering aid. Excess carbon can be used to address and compensate for irregularities in deposition equipment and processes and can be used to control or execute the deposition process.
[0188] In applications where nitrogen is considered a contaminant, polysilocarb-derived SiC and SiOC embodiments may have less than about 10,000 ppm, less than 1000 ppm, less than about 100 ppm, less than about 10 ppm, less than about 1 ppm, and less than about 0.1 ppm nitrogen, and less than that, and from about 1000 ppm to about 0.01 ppm nitrogen, from about 100 ppm to about 0.001 ppm nitrogen. SiC bulk form embodiments have the same purity levels.
[0189] In one embodiment of polysilocarb-derived SiC, there is no or essentially no oxygen present, either bonded to Si or C or as an oxide layer. Thus, polysilocarb-derived SiC and SiC volume shape embodiments may have less than about 10,000 ppm, less than 1000 ppm, less than about 10 ppm, less than about 1 ppm, less than about 0.1 ppm oxygen and less than about 1000 ppm to about 0.01 ppm oxygen, about 100 ppm to about 0.001 ppm oxygen. Polysilocarb-derived SiC has the resistance to forming an oxide layer when exposed to air under standard temperature and pressure. SiC that is free of an oxide layer when stored under atmospheric conditions, i.e. does not contain an oxide layer, provides advantages in later manufacturing processes where an oxide layer is considered an impurity or where an oxide layer is considered to have a detrimental effect on the manufacturing process. SiC volume shape embodiments have the same purity levels.
[0190] The present polysilocarb-SiC, and embodiments of SiC boules, wafers and other structures made from polysilocarb-derived SiC, exhibit polymorphism, and generally one-dimensional polymorphism, which is referred to as polymorphism. Thus, polysilocarb-derived SiC may exist in many theoretically infinite different polytypes. As used herein, unless otherwise indicated, polytype, polytypes, and similar terms should be given the broadest possible meaning and include the various different frames, structures, or arrangements that make up the silicon carbide tetrahedron (SiC4). Typically, these polytypes are divided into two categories: alpha (α) and beta (β).
[0191] Alpha category embodiments of polysilocarb-derived SiC typically include hexagonal (H), rhombohedral (R), trigonal (T) structures, and may include combinations of these. The beta category typically includes cubic (C) or zinc blende structures. Thus, for example, polysilocarb-derived silicon carbide polytypes include 3C-SiC (β-SiC or β3C-SiC) with a stacking sequence of ABCABC..., 2H-SiC with a stacking sequence of ABAB..., 4H-SiC with a stacking sequence of ABCBABCB..., and -SiC (the common form of alpha silicon carbide, α6H-SiC) with a stacking sequence of ABCACBABCACB.... Examples of other forms of alpha silicon carbide include 8H, 10H, 16H, 18H, 19H, 15R, 21R, 24H, 33R, 39R, 27R, 48H, and 51R.
[0192] Polysilocarb-derived SiC embodiments can be polycrystalline or single (mono-) crystalline. Generally, in polycrystalline materials, grain boundaries exist as interfaces between two grains, or crystallites, of the material. These grain boundaries can be between the same polytype with different orientations, or between different polytypes with the same or different orientations, and combinations and variations thereof. Single crystal structures are composed of a single polytype and are essentially free of grain boundaries.
[0193] Embodiments of the method result in boules, preferably single crystal boules of SiC. These boules can have lengths of about 1 / 2 inch to about 5 inches, about 1 / 2 inch to about 3 inches, about 1 inch to about 2 inches, greater than about 1 / 2 inch, greater than about 1 inch, greater than about 2 inches. Larger and smaller sizes and all values within these size ranges are contemplated. The boules can have cross-sectional areas of, for example, diameters of about 1 / 2 inch to about 9 inches, about 2 inches to about 8 inches, about 1 inch to about 6 inches, greater than about 1 inch, greater than about 2 inches, greater than about 4 inches, about 4 inches, about 6 inches, about 8 inches, about 12 inches, about 18 inches. Other sizes and all values within these size ranges are contemplated.
[0194] Generally, the process of fabricating electronic components from a SiC boule involves sawing the SiC single crystal boule into thin wafers. The wafers have the diameter of the boule and typically have a thickness of about 100 μm to about 500 μm. One or both sides of the wafer are then polished. The polished wafers are then used as substrates for the fabrication of microelectronic semiconductor devices. The wafers thus serve as substrates for microelectronic devices that are integrated within the wafer, integrated on the wafer, or both. The fabrication of these microelectronic devices includes microfabrication processing steps such as epitaxial growth, doping or ion implantation, etching, deposition of various materials, and photolithographic patterning, to name a few. Once fabricated from the wafer, the wafers, and thus the individual microcircuits, are separated into individual semiconductor devices in a process known as dicing. These devices are then used, for example integrated, in the fabrication of various larger semiconductor and electronic devices.
[0195] Embodiments of the method and resulting SiC wafers are applicable to, among other things, wafers of about 2 inch diameter and smaller, about 3 inch diameter wafers, about 4 inch diameter wafers, about 5 inch diameter wafers, about 6 inch diameter wafers, about 7 inch diameter wafers, about 12 inch diameter wafers, and possibly larger diameters, about 2 inch to about 8 inch diameter wafers, about 4 inch to about 6 inch diameter wafers, square, circular, and other shapes, about 1 square inch, about 4 square inch, about 8 square inch, about 10 square inch, about 12 square inch, about 30 square inch, about 40 square inch, about 50 square inch, about 60 square inch, about 70 square inch, about 80 square inch, about 90 square inch, about 100 square inch, about 12 ... Inches squared, about 50 square inches and greater and less than surface area, about 100 μm thick, about 200 μm thick, about 300 μm thick, about 500 μm thick, about 700 μm thick, about 50 μm to about 800 μm thick, about 100 μm to about 700 μm thick, about 100 μm to about 400 μm thick, about 100 μm to about 300 μm thick, about 100 μm to about 200 μm thick, and greater and less than thickness, as well as combinations and variations thereof, and all values within these ranges.
[0196] Embodiments of the method and the resulting cut and polished wafers may be used to initiate the growth of a boule (i.e., as "seeds") from which the remainder of the growing boule conforms. Wafers, or seeds, may include, among others, wafers of about 2 inches and smaller, wafers of about 3 inches, wafers of about 4 inches, wafers of about 5 inches, wafers of about 6 inches, wafers of about 7 inches, wafers of about 12 inches, and possibly larger diameters, wafers of about 2 inches to about 8 inches, wafers of about 4 inches to about 6 inches, squares, circles, other shapes, wafers of about 4 square inches, about 8 square inches, about 12 square inches, about 30 square inches, about 50 square inches, and larger and smaller surfaces. This includes wafers having a thickness of about 100 μm, about 200 μm, about 300 μm, about 500 μm, about 1500 μm, about 2500 μm, about 50 μm to about 2000 μm, about 500 μm to about 1800 μm, about 800 μm to about 1500 μm, about 500 μm to about 1500 μm, about 1200 μm, about 200 μm to about 2000 μm, about 50 μm to about 2500 μm, greater and lesser thicknesses, and combinations and variations thereof, and all values within these dimensional ranges.
[0197] Embodiments of the inventive SiC boules, SiC wafers, and microelectronics produced from those wafers may find application and use in diodes, wideband amplifiers, military communications, radar, communications, data links and tactical data links, satcom and point-to-point wireless power electronics, LEDs, lasers, lighting, sensors, among others. Additionally, these embodiments may find application and use in transistors such as high electron mobility transistors (HEMTs), including HEMT-based monolithic microwave integrated circuits (MMICs). These transistors may employ a distributed (traveling wave) amplifier design approach, and due to the large band gap of SiC, very wide bandwidths can be achieved in a small footprint. Thus, embodiments of the invention include those devices and articles produced from or based on the inventive methods, deposition techniques, and polymer-derived SiC, SiC boules, SiC wafers, and microelectronics produced from those wafers.
[0198] Polysilocarb-derived SiC, particularly high purity SiC embodiments, have many unique properties that make them advantageous and desirable for use in electronics, solar, and power transmission industries and applications, among others. They function as very stable semiconductor materials and are suitable for several demanding applications, including high power, high frequency, high temperature, corrosive environments and applications. Polymer-derived SiC is an extremely hard material with a Young's modulus of 424 GPa. It is essentially chemically inert and will not react with any materials at room temperature.
[0199] Embodiments of the present invention have the ability to provide high purity SiOC and SiC in the form of volumetric structures such as pucks, briquettes, bricks, blocks, tablets, pills, plates, disks, squares, balls, rods, random shapes, etc. These volumetric shapes include shapes that are roughly 1 / 32 in. 3 (inch 3 ) or more, 1 / 16in 3 That's it, 1 / 8in 3 Over, 1 / 4in3 Above, about 1 / 16 inch 3 About 1 ft from 3 , larger and smaller volumes, and all values within these dimensional ranges. Embodiments of the volumetric structures can be rigid and structurally sound, or soft and brittle. For disks, plates, pills, and other more generally flat volumetric structures, the area of the largest surface (i.e., width, not thickness) is approximately 1 / 32 in. 2 or more, or about 1 / 16 in. 2 Above, about 1 / 8 inch 2 Above, about 1 / 4 inch 2 Above, about 1 / 2 inch 2 Above, about 1in 2 More than or equal to about 2in 2 , and about 1 / 4in 2 From about 3in 2 , about 1 / 2in 2 From about 4in 2 and approximately 1 / 8in 2 From about 3 / 4 in 2 These planar volumetric shapes can have a thickness of less than 1 / 64 inch, less than 1 / 32, less than 1 / 2 inch, from about 1 / 16 inch to about 3 / 4 inch, from about 1 / 8 inch to about 1 / 2 inch, 1 / 8 inch or more, 1 / 4 inch or more, combinations and variations thereof, and all values within these dimensional ranges.
[0200] In preferred embodiments, the volume shapes have adequate strength for use, e.g., the ability to withstand handling and remain structurally intact so that they can be shipped, unpackaged, and loaded into a boule growth deposition apparatus. Depending on the binder or other bonding process used, these volume shapes can also have significant strength.
[0201] Embodiments of the SiC volumetric structure can have an elastic modulus of about 100 kPa to about 100 MPa, about 500 kPa to about 500 Mpa, about 100 kPa to about 1 GPa, about 50 kPa to about 300 GPa, and greater and lesser values, and combinations, variations thereof, and all values within the ranges of these properties.
[0202] The SiC volumetric structure embodiment has a capacity of approximately 10 Kg / mm 2 Approximately 2,500 kg / mm 2 , about 10Kg / mm 2 Approximately 1,500 kg / mm 2 , about 100 kg / mm 2 to about 2,000 kg / mm 2 , about 150Kg / mm 2 to about 1,000 kg / mm 2 , about 300Kg / mm 2 Approximately 1,750 kg / mm 2 , greater and lesser values, combinations and variations thereof, and all values of hardness within the range of these properties.
[0203] Embodiments of the SiC volumetric structure can have stiffnesses of about 5 kPa to about 15 MPa, about 10 kPa to about 10 MPa, about 100 kPa to about 1 MPa, and about 10 kPa or more, about 100 kPa or more, about 1 MPa or more, and larger and smaller values, combinations and variations thereof, and all values within these property ranges.
[0204] Embodiments of the SiC volumetric structure can have a compressive strength from about 1 MPa to about 3.5 GPa, from about 10 MPa to about 2.5 GPa, from about 50 MPa to about 1 GPa, from about 50 MPa to about 750 MPa, from about 100 MPa to about 2 GPa, from about 200 MPa to about 800 MPa, greater and lesser values, combinations and variations thereof, and all values within these property ranges.
[0205] In embodiments of these structures that can be considered higher strength embodiments, these SiC bulk structures have elastic moduli of less than about 200 MPa, less than about 150 MPa, less than about 75 MPa, and less than about 10 MPa, and less than about 1,400 Kg / mm 2 Less than 800 kg / mm 2 Less than 400 kg / mm 2 Less than 100 kg / mm 2 The composition may have properties of all values within these ranges, including hardness of less than about 1,850 MPa, less than about 1,000 MPa, less than about 750 MPa, less than about 200 MPa, less than about 50 MPa, and combinations and variations thereof.
[0206] These SiC volumetric structures can have the following: elastic moduli of about 100 MPa or more, about 200 MPa or more, and about 300 MPa or more; about 700 Kg / mm 2 Above, approximately 1,000Kg / mm 2 More than 2,000Kg / mm 2 hardness of about 50 MPa or greater, about 200 MPa or greater, and about 500 MPa or greater; compressive strengths of about 50 MPa or greater, about 200 MPa or greater, and about 500 MPa or greater; combinations and variations thereof, and properties of all values within these ranges.
[0207] In those volumetric structural embodiments that can be considered to have lower strength, these embodiments can have lower or less stiffness values, e.g., stiffness of 10 MPa or less. In these low strength structural embodiments, for example, hydrocarbon waxes can be used, which are significantly less stiff than, for example, ceramic binders.
[0208] In some embodiments, these SiC volume shapes are generally weaker than the SiC material that composes their structure, with an elastic modulus of about 410 GPa and a stiffness of about 2,800 Kg / mm 2and a compressive strength of about 3,900 MPa, combinations and variations thereof, and all values within the ranges of these properties have been reported. The actual density of SiC as measured by helium pycnometry is about 3.0-3.5 g / cc, or about 3.1-3.4 g / cc, or about 3.2-3.3 g / cc, and combinations and variations thereof, and all values within the ranges of these properties. The apparent density, or specific gravity, of volumetric shaped embodiments of SiC, such as pellets, pills, etc., may be significantly lower.
[0209] In one embodiment, the mass of SiC volume shapes preferably and typically have an apparent density lower than the actual density of the SiC, e.g., the actual density of SiC granules is about 3.1 g / cc to 3.3 g / cc. The apparent density of the volume shapes (e.g., pucks, pellets, cubes, balls, beads, disks, or plates) can be less than about 3 g / cc, less than about 2 g / cc, or less than about 1 g / cc, and can be about 0.5 g / cc to about 1.8 g / cc, or about 0.4 g / cc to about 2 g / cc. The bulk density of the particles of SiC can be less than about 3.0 g / cc, less than about 2.0 g / cc, less than about 1 g / cc, and about 0.1 g / cc to about 2 g / cc, or 0.5 g / cc to about 1.5 g / cc. Larger and smaller apparent and bulk densities are also contemplated. Additionally, a specific, i.e., predetermined, precise apparent density of the polymer-derived SiC volume shapes can be provided to match, preferably enhance, and more preferably optimize for subsequent manufacturing processes. For example, in PVT wafer manufacturing, the SiC granule volume shapes can have an apparent density that is specifically designed and tailored to match a specific PVT machine. In this manner, each PVT machine in a facility can have a custom feedstock, which allows the performance of each machine to be optimized using a feedstock (e.g., SiC volume shapes) with predetermined, precise properties such as volume, weight, packing percentage, bulk density, tap density, apparent density, etc.
[0210] In an embodiment, the SiC volume shapes can have porosity, which is preferably provided by or with the binder. The porosity is preferably open or substantially open porosity. Thus, the volume shapes typically provide a substantially greater available surface area than granular SiC. This is because the structure of the shapes includes pore surfaces that are not present in a loose pile of SiC particles, for example, where the granules are packed together. Thus, for example, when disks of SiC are used in a deposition process to create SiC boules (for subsequent conversion to SiC wafers), these SiC disks provide a significantly greater surface area for SiC vapor generation and pathways for SiC vapor transport to generate SiC vapor than would typically be obtained by using granular SiC in such a process. It is theorized that the increased surface area and increased pathways can improve the growth rate of the SiC boule, the quality of the SiC boule (and thus the subsequent wafer), or both. Volumetric shapes of SiC, such as SiC disks, are easier to handle, measure, and use than granular SiC material.
[0211] In embodiments, the volume shapes can be made from granules of SiC obtained by breaking up friable chunks of SiC coming out of a pyrolysis furnace. This allows for control over the size of the granules used to create the volume shapes. This also provides greater control over the binder addition and mixing process in some embodiments.
[0212] In one embodiment, the friable agglomerates of SiC preferably and typically have an apparent density significantly lower than their actual density, e.g., an actual density of about 3.2 g / cc. Generally, granular SiC obtained by crushing the friable agglomerates has essentially the same apparent and actual densities, e.g., about 3.1-3.3 g / cc.
[0213] The characteristics of high purity polysilocable SiC provide several advantages and benefits for use as, for example, Si and C sources or starting materials, deposition processes, systems and apparatus, among other techniques for growing or creating SiC chunks, structures, objects or volumetric shapes, such as: high purity levels, ability to control particle size distribution (shape, size and both); predetermined particle size distribution; ability to have volumetric shapes; predetermined volumetric shapes (e.g., pucks, pills, disks, etc.); ability to have porosity and control porosity; predetermined porosity; ability to control the amount of carbon; predetermined amount of carbon (excess i.e., greater than stoichiometric, less than stoichiometric i.e., deficient, and equal to stoichiometric); combinations and variations of these and other properties. Additional advantages of the present invention are seen in deposition processes, including reduced time to grow a boule or other structure, longer run times before cleaning, ability to optimize equipment, ability to grow larger diameter boules or other structures, ability to increase quality, ability to reduce problem areas, problem areas or problem occurrences (e.g., pipes, blockages, defects) from the boule or other structure, reduced costs, increased control over the entire process, and combinations and variations thereof.
[0214] In one embodiment, if a dopant needs to be added to the material, it can be added via the precursor, and therefore can be added in a controlled manner and amount for growth into a boule or other structure. An embodiment of the precursor formulation can have a dopant, or a composite that carries and bonds the dopant to the ceramic and then to the converted SiC, making the dopant available and usable in the deposition process.
[0215] Additionally, dopants or other additives provide custom or predetermined properties to wafers, layers and structures made from the polymer-derived SiC embodiments. In these embodiments, such property-enhancing additives are not considered impurities since they must be included in the final product. The property-enhancing additives can be incorporated into the liquid precursor material. Depending on the nature of the property-enhancing additive, it can be part of the precursor framework, complexed for incorporation into the liquid precursor, part of a composite, or in other form (e.g., in a form that functions as intended in the final material). The property-enhancing additive can be added to the SiC or SiOC powder material as a coating, added as a vapor or gas during processing, or powdered and mixed with the polymer-derived SiC or SiOC particles. In one embodiment, the property-enhancing additive includes or is part of a binder for the volume shape. In one embodiment, the property-enhancing additive can be a coating on the volume shape. Additionally, the form and manner in which the property-enhancing additive is present should preferably be such that it has minimal, and more preferably no, adverse effect on the processing conditions, processing times, and quality of the final product. Thus, polysilocarb derived SiC, or SiC volume shapes of 5 nines purity or greater, 6 nines purity or greater, 7 nines purity or greater, can have amounts of property enhancing additives, which can be from about 0.01% to about 50%, from about 0.1% to about 5%, from about 1% to about 10%, less than 25%, less than 20%, less than 10% and less than 1%, and greater and lesser amounts depending on the additive and the given property it is intended to impart.
[0216] The use of ultra-pure polymer-derived SiC, the use of the current volumetric forms of SiC, and the present deposition techniques individually and collectively provide superior quality and reduced defects in boules, wafers, and semiconductors made from these ultra-pure polymer-derived materials when compared to boules and wafers made from other SiC sources, i.e., non-polymer-derived ceramic-based SiC. Without being bound by this theory, it is believed that the polymer-derived ceramic process used to obtain ultra-pure SiC from liquid SiOC starting materials, e.g., polysilocarb precursors, provides starting SiC with characteristics and morphology that differ from other sources of SiC. This difference is believed to allow polymer-derived ceramic materials to be significantly better preformed in vapor deposition processes than other sources of SiC, and furthermore, it is believed that the present volumetric forms and deposition techniques provide the ability to further benefit from and build synergistically from the advantages of ultra-pure polymer-derived SiC. It is further believed that the use of polymer-derived ceramic SiC as a seed crystal can achieve further improvements in boule and wafer quality and manufacturing efficiency over other SiC seeds.
[0217] Accordingly, it is believed and theorized that the use of ultra-high purity polymer-derived SiC, the use of the inventive volumetric shapes of SiC, and the use of the inventive deposition techniques, individually and collectively, enable an enhancement and improvement of at least one or more, and preferably all, of the following properties and capabilities (present in deposition processes using conventional SiC starting materials), and a reduction of at least one or more, and preferably all, of the following deleterious properties or effects:
[0218] Bow: A concave or convex deformation of the central surface of a wafer, independent of any thickness variations that may be present. Bow is determined at the center point of the wafer with respect to a reference plane determined by three equally spaced points on a circle whose diameter is 6.35 mm less than the nominal wafer diameter. Bow is a bulk property of the wafer, not a property of the exposed surface. Bow is usually determined with the wafer in a free, unclamped position. (Not to be confused with warp.)
[0219] Diameter: The linear distance containing the center of a circular silicon wafer, not including any flats or other peripheral reference areas.
[0220] Edge Profile: The cross-sectional profile of a wafer edge shaped by grinding or etching. The edge may be rounded or chamfered.
[0221] Flatness: For a wafer surface, the deviation of the front surface, expressed as TIR or maximum FPD, from a specified reference plane when the back surface of the wafer is ideally flat, as when lowered by vacuum onto an ideally clean flat chuck. Wafer flatness can be described as: overall flatness; maximum site flatness measured across all sites; percentage of sites with site flatness less than or equal to a specified value.
[0222] Flatness Quality Area: That portion of the surface of the wafer to which a specified flatness value applies. The flatness quality area is most often defined by an edge exclusion area, typically a peripheral ring 3 mm wide.
[0223] Focal Plane: The plane perpendicular to the optical axis of an imaging system that contains the focal point of the imaging system.
[0224] Focal Plane Deviation (FPD): The distance parallel to the optical axis from a point on the wafer surface to the focal plane. Global Flatness: The TIR or maximum FPD within the flatness quality area relative to a specified reference plane.
[0225] Maximum FPD: The maximum absolute value of focal plane deviation.
[0226] Primary Plane: The plane of greatest length oriented relative to a particular crystal face. Also called major flat.
[0227] Reference Surface: A surface specified by either: three points at specified locations on the front surface of the wafer; a least squares fit to the front surface using all points within the flatness quality area; a least squares fit to the front surface of the wafer using all points within the site; or an ideal back surface (corresponding to an ideally flat chuck surface in contact with the wafer).
[0228] Secondary Flat: A flat of lesser length than the primary flat whose angular position relative to the primary flat identifies the conductivity type and orientation of the wafer. Also called a minor flat.
[0229] Site: A rectangular area on the front surface of a wafer whose sides are parallel to and perpendicular to the major plane and whose center is within the planar quality area.
[0230] Site Flatness: The TIR or maximum FPD of the portion of the site that is within the flatness quality area.
[0231] Thickness: The distance through the wafer between corresponding points on the front and back surfaces.
[0232] Total Indicated Reflectance (TIR): The minimum perpendicular distance between two planes, both parallel to a reference plane, that enclose all points within a specified flatness quality area or site on the front side of the wafer.
[0233] Total Thickness Variation (TTV): The difference between the maximum and minimum thickness values encountered during a series of point measurements on a scan pattern or wafer.
[0234] Warp: The difference between the maximum and minimum distances of the central surface of the wafer from a reference plane encountered during a scan pattern. Warp is a bulk property of the wafer, not a property of the exposed surface. The central surface may contain areas of upward or downward curvature, or both. Generally, warp is determined with the wafer in its free, unclamped position. (Not to be confused with bow.)
[0235] Udoping: Dopants from sources other than dopants intentionally added to the gas phase and incorporated into the epitaxial layer during growth.
[0236] Autodoping Barrier: A film or layer that prevents the transport of impurity atoms from the backside of the substrate into the epilayer during epitaxial deposition. Also called backseal.
[0237] Conductivity Type: Defines the majority nature of the carriers in silicon. N-type material, where electrons are the majority carriers, is formed when donor dopant impurities are added to silicon. P-type material, where holes are the majority carriers, is formed when acceptor dopant impurities are added to silicon.
[0238] Crystal orientation: The crystal axis along which a silicon crystal grows.
[0239] Dislocation: A line imperfection in a crystal that forms the boundary between slipped and non-slip regions of the crystal.
[0240] Dislocation Density - The number of dislocation etch pits per unit area on the exposed wafer surface.
[0241] Dislocation Etch Pit: A sharply defined depression in the immediate vicinity of a stressed or defective crystal lattice, resulting from preferential etching.
[0242] Dopant: A chemical element from the third column (e.g., boron) or fifth column (e.g., phosphorus or antimony) of the periodic table. It is intentionally incorporated into silicon crystals in transformer amounts to establish the conductivity type and resistivity. P-type Bor 0,001—50 Ω cm. N-type Phosphorus 0.1—40 Ω cm, Antimony 0.005—0,25 Ω, Arsenic <0,005 Ω cm.
[0243] Extrinsic Gettering: Controlled damage or stress to the crystal lattice structure intentionally introduced by mechanical means or by deposition of polysilicon or other films on the backside of a silicon wafer.
[0244] Plane orientation (primary): A crystal plane that ideally coincides with the surface of a primary plane. A primary plane is usually <110> It is a surface.
[0245] Miller indices: the reciprocals of the intercepts of a crystal plane with the x-axis, y-axis, and z-axis, respectively. For example, a cube plane perpendicular to the x-axis is <100> A family of planes is denoted by curly brackets: for example, all the faces of a cube are <100> The plane is indicated by Miller indices in brackets. For example, the x-axis is <100> direction, and the diagonal of the cube is <111> A family of directions is denoted by square brackets. For example, all cube axes are <100> The negative direction is indicated by a minus sign on the index. For example, the negative x-axis is the <-100> direction.
[0246] Polycrystalline silicon (polysilicon, poly): Silicon composed of randomly oriented crystallites and containing high-angle grain boundaries, twin boundaries, or both.
[0247] Radial Oxygen Variation: The difference between the average oxygen concentration at one or more symmetrically placed points on a silicon wafer and the oxygen concentration at the center of the wafer. Expressed as a percentage of the center concentration. Unless otherwise specified, radial oxygen variation is determined using the average of oxygen concentration at two points 10 mm from the edge of the wafer. Radial oxygen variation may also be determined using the average of oxygen concentration at several symmetric points midway between the center and edge of the wafer. Also called oxygen gradient.
[0248] Radial Resistivity Variation: The difference between the average resistivity of one or more points symmetrically placed on a silicon wafer and the resistivity at the center of the wafer. Expressed as a percentage of the resistivity at the center. The radial resistivity change can be determined using the average resistivity of four points at two perpendicular diameters and 6 mm from the edge of the wafer. Radial resistivity variation is sometimes determined using the average of the resistivity at four points halfway between the center and the edge of the wafer of the same diameter. Also called resistivity gradient.
[0249] Resistivity (ohm·cm): The ratio of the potential gradient (electric field) parallel to the current to the current density. In silicon, resistivity is controlled by adding dopant impurities. Adding dopants lowers the resistivity.
[0250] Slip: A process of plastic deformation in which one part of a crystal undergoes shear displacement relative to another part in a manner that preserves the crystallinity of the silicon. After preferential etching, slip is evidenced by one or more parallel straight line patterns of 10 or more dislocation etch pits per millimeter that are not necessarily mutually exclusive. <111> On the surface, the groups of lines are inclined at 60 degrees to each other. <100> On the surface, they are inclined at 90° to each other.
[0251] Stacking Fault: A two-dimensional defect resulting from a deviation from the normal stacking sequence of atoms in a crystal. They exist in the bulk crystal and can grow during epitaxial deposition (usually the result of contamination or structural imperfections on the substrate surface) or arise during oxidation. <111> At the surface, selective etching reveals stacking faults as closed or partial equilateral triangles. <100> On the surface, stacking faults appear as closed or partial squares.
[0252] Striations: Spiral morphology on the surface of a silicon wafer associated with local variations in impurity concentration. Such variations are due to periodic differences in dopant incorporation that occur at the rotating solid-liquid interface during crystal growth; the striations are visible to the naked eye after selective etching and appear continuous at 100x magnification.
[0253] Subsurface Damage: Residual crystallographic defects that are only apparent after preferential etching of a polished silicon surface. Such damage is typically believed to be caused by mechanical processing of the wafer.
[0254] Twin: A crystal consisting of two parts that are oriented relative to each other as mirror images across a coherent planar interface known as the twin plane or twin boundary. In silicon, this plane is <111> It is also called a twin.
[0255] Wafer Orientation: The crystal plane, described in terms of Miller indices, with which the surface of the wafer is ideally coincident. Typically, the surface of the wafer corresponds to within a few degrees with a low-index plane perpendicular to the growth axis. In such cases, the orientation can be described in terms of the angular deviation α of the low-index crystal plane from the polished wafer surface.
[0256] Chip: An area where material has been removed from the surface or edge of a wafer. The size of a chip is defined by its maximum radial depth and peripheral chord length measured on an orthogonal projection of the specimen profile. Also known as clamshell, conchoidal fracture, edge chip, flake, nick, peripheral chip, peripheral indent, and surface chip.
[0257] Contamination: A broad category of foreign matter visible to the naked eye on the wafer surface. In most cases it can be removed by blowing off gases, cleaning with detergents, or chemical action. See also Particulate Contamination, Soil.
[0258] Crack: A split that extends to the surface of the wafer and may or may not pass through the entire thickness of the wafer. Also called a fissure. See also fracture.
[0259] Cratering: A surface texture of irregular closed ridges with a smooth central region. <111> "Crow's feet" (Y) on the surface <100> Intersecting cracks on the surface in a pattern resembling a cross (+).
[0260] Dimple: A smooth surface depression on the wafer surface greater than 3 mm in diameter.
[0261] Fracture: Single or multiple linear cracks radiating from a point.
[0262] Groove: A shallow scratch with rounded edges, usually a scratch remnant that is not completely removed during sanding.
[0263] Haze: A cloudy or hazy appearance caused by light scattering due to concentrations of minute surface irregularities such as pits, mounds, small bumps or scratches, and grains.
[0264] Embedded Abrasive: Abrasive grains mechanically pressed into the surface of a silicon wafer. This type of contamination can occur during slicing, lapping, or polishing.
[0265] Indentation: An edge defect that extends from the front to the back of a silicon wafer.
[0266] Light Point Defect (LPD): Individual tiny points of reflected light that can be seen when a wafer is illuminated by a narrow-beam light source held perpendicular to the wafer surface.
[0267] Mound: An irregularly shaped protrusion with one or more facets. Mounds are extensions of the bulk material and / or various forms of contamination. Dense mounds may also appear as haze.
[0268] Orange Peel: A rough surface with large features resembling orange skin. Visible to the naked eye under fluorescent lighting, but usually not visible under narrow beam lighting.
[0269] Particulate Contamination: A form of contamination that includes particles such as dust, lint, or other material that remain on the surface of the wafer and protrude from the surface, and can usually be blown off the surface with clean, dry nitrogen.
[0270] Pit: A surface depression where the sloping sides of the depression meet the wafer surface in a well-defined manner (as opposed to the rounded sides of a dimple).
[0271] Saw Blade Defects: Rough areas visible after grinding in a pattern characteristic of the movement of the saw blade. May be discernible before chemical grinding. Also called saw marks.
[0272] Scratch: A shallow groove or incision below the plane of the established surface, with a length to width ratio greater than 5:1. Macro-scratches are =0.12 μm deep and are visible to the naked eye under both incandescent (narrow beam) and fluorescent lighting. Micro-scratches are <0.12 μm deep and are invisible to the naked eye under fluorescent lighting.
[0273] Spike: A tall, thin dendrite or crystalline filament that often occurs in the center of a depression in the surface of an epitaxial layer.
[0274] Stain: a form of contamination such as streaks, stains, or spots containing organic matter or foreign chemical compounds such as salts.
[0275] Threading Edge Dislocation (TED).
[0276] Thread cutting screw displacement (TSD).
[0277] Basic Plan Dislocation (BPD).
[0278] Micro pipe.
[0279] Macro defects in the boule.
[0280] Carbon Inclusion
[0281] Silicon droplets
[0282] void
[0283] Wafers with the following characteristics can be fabricated using polymer-derived ultra-pure SiC material: JPEG2025024179000003.jpg221152JPEG2025024179000004.jpg232154JPEG2025024179000005.jpg229152JPEG2025024179000006.jpg60152
[0284] SSP = Single Side Polished, DSP = Double Side Polished, E = Etched, C = AsCut, L = Lap, Und = Undoped (essentially)
[0285] It is theorized that there may be additional embodiments for forming SiC powder into volumetric shapes: using graphite parts or graphite foam as inserts in the growth chamber to press the powder into a specific geometric shape (e.g., spacer); making "wet sand" using water or other high purity volatile liquid and using a "sandcastle" mold to create the shape in the growth chamber; then gently evaporating the volatile liquid before growing the boule; permeable sacrificial molds made of porous carbon or porous SiC (e.g., K-CUP made of compatible material). Examples
[0286] The following examples are provided to illustrate various embodiments of the systems, processes, formulations, applications, and materials of the present invention. These examples are for illustrative purposes and should not be considered as limiting the scope of the present invention. The percentages used in the examples are weight percents of the total, e.g., formulations, mixtures, products, or structures, unless otherwise specified. The usage X / Y or XY indicates the % of X and the % of Y in the formulation, unless otherwise specified. The usage X / Y / Z or XYZ indicates the % of X, the % of Y, and the % of Z in the formulation, unless otherwise specified.
[0287] Example 1
[0288] A polysilocarb formulation is formulated using a blending type method. The formulation is made by blending 41% MHF and 59% TV at room temperature. The precursor formulation has 0.68 moles of hydride, 0.68 moles of vinyl, and 1.37 moles of methyl. The precursor formulation has the following molar amounts of Si, C, and O based on 100 g of formulation: JPEG2025024179000007.jpg52123
[0289] As calculated, the SiOC derived from this formulation has a calculated 1.37 moles of C after all CO is removed, with 0% excess C. This material is then pyrolyzed into a ceramic and further converted to SiC particles and packed.
[0290] Example 2
[0291] A polysilocarb formulation is formulated using a blending method. The formulation is made by blending together 90% methyl terminated phenylethyl polysiloxane at room temperature. The precursor formulation contains 1.05 moles of hydride, 0.38 moles of vinyl, 0.26 moles of phenyl, and 1.17 moles of methyl. The precursor formulation has the following molar amounts of Si, C, and O based on 100 g of formulation: JPEG2025024179000008.jpg45109
[0292] As calculated, the SiOC obtained from this formulation has a calculated 2.31 moles of C after all CO is removed, with 98% excess C. This material is pyrolyzed into ceramic and further converted into SiC particles with excess C and formed into pucks.
[0293] The excess carbon in the starting materials and starting volume shapes can be obtained by several embodiments. For example, the excess carbon can be obtained from a formulation with excess residual C through the PDC route. For example, using a formulation with excess C (e.g., DCPD type formulation) produces SiC and C as equilibrium phases after complete pyrolysis to >1600°C. In another embodiment, the excess C can be obtained by adding C powder or C-containing species to the liquid PDC formulation before curing and pyrolysis. In another embodiment, SiOC pigment with excess free C can be added to the volume shapes. Additionally, a binder that decomposes to C upon pack formation can be used. Also, a C-containing powder combined with a binder can be used to incorporate more C into the formulation.
[0294] Example 3
[0295] A polysilocarb formulation is formulated using a blending type method. The formulation is made by blending 70% methyl terminated phenylethyl polysiloxane (containing 14% X) and 30% TV at room temperature. The precursor formulation contains 0.93 moles of hydride, 0.48 moles of vinyl, 0.13 moles of phenyl, and 1.28 moles of methyl. The precursor formulation has the following molar amounts of Si, C, and O based on 100 g of formulation: JPEG2025024179000009.jpg49113
[0296] As calculated, the SiOC obtained from this formulation has a calculated 1.77 moles of C after all CO is removed, with 38% excess C. This material is then pyrolyzed into a ceramic and further converted to SiC particles. The SiC particles have excess C and are packed together. In some of these non-stoichiometric formulations (i.e., the Si:C molar ratio is not 1:1), the actual density of the starting material is <3.21 g / cc due to the excess carbon.
[0297] Example 4
[0298] A polysilocarb formulation is formulated using a blending type method. The formulation is made by blending together 50% methyl terminated phenylethyl polysiloxane (containing 20% X) and 50% TV at room temperature. This precursor formulation has 0.67 moles of hydride, 0.68 moles of vinyl, 0.10 moles of phenyl, and 1.25 moles of methyl. The precursor formulation has the following molar amounts of Si, C, and O based on 100 g of formulation: JPEG2025024179000010.jpg45109
[0299] As calculated, the SiOC obtained from this formulation has a calculated 1.93 moles of C after all CO is removed, with 55% excess C. This material is then pyrolyzed into ceramic and further converted to SiC particles, with excess C, and packed.
[0300] Example 5
[0301] A polysilocarb formulation is formulated using a blending type method. The formulation is made by blending together 65% methyl terminated phenylethyl polysiloxane (containing 40% X) and 35% TV at room temperature. The precursor formulation contains 0.65 moles of hydride, 0.66 moles of vinyl, 0.25 moles of phenyl, and 1.06 moles of methyl. The precursor formulation has the following molar amounts of Si, C, and O based on 100 g of formulation: JPEG2025024179000011.jpg44111
[0302] As calculated, the SiOC obtained from this formulation has a calculated 2.81 moles of C after all CO is removed, with 166% excess C. This material is then pyrolyzed into ceramic and further converted to SiC particles, with excess C, and packed.
[0303] Example 6
[0304] A polysilocarb formulation is formulated using a blending type method. The formulation is made by blending 65% MHF and 35% dicyclopentadiene (DCPD) at room temperature. The precursor formulation contains 1.08 moles of hydride, 0.53 moles of vinyl, 0.0 moles of phenyl, and 1.08 moles of methyl. The precursor formulation has the following molar amounts of Si, C, and O based on 100 g of formulation: JPEG2025024179000012.jpg48108
[0305] As calculated, the SiOC obtained from this formulation has a calculated 2.65 moles of C after all CO is removed, with 144% excess C. This material is then pyrolyzed into ceramic and further converted to SiC particles, with excess C, and packed.
[0306] Example 7
[0307] A polysilocarb formulation is formulated using a blending type method. The formulation is made by blending 82% MHF and 18% dicyclopentadiene (DCPD) at room temperature. The precursor formulation contains 1.37 moles of hydride, 0.27 moles of vinyl, 0.0 moles of phenyl, and 1.37 moles of methyl. The precursor formulation has the following molar amounts of Si, C, and O based on 100 g of formulation: JPEG2025024179000013.jpg47110
[0308] As calculated, the SiOC obtained from this formulation has a calculated 1.37 moles of C after all CO is removed, with 0% excess C. This material is then pyrolyzed into ceramic and further converted to SiC particles, which are stoichiometric and packed.
[0309] Example 8
[0310] A polysilocarb formulation is formulated using a blending type method. The formulation is made by blending 46% MHF, 34% TV, 20% VT at room temperature. The precursor formulation contains 0.77 moles of hydride, 0.40 moles of vinyl, 0.0 moles of phenyl, and 1.43 moles of methyl. The precursor formulation has the following molar amounts of Si, C, and O based on 100 g of formulation: JPEG2025024179000014.jpg46109
[0311] As calculated, the SiOC derived from this formulation has a calculated 0.53 moles of C after all CO is removed, making it 63% C deficient. This material is then pyrolyzed into ceramic and further converted to C-deficient SiC particles and packed.
[0312] A Si-rich formulation can be obtained, for example, by having a starting material or starting pack that is C-deficient (e.g., a SiOC ceramic derived only from MHF as its precursor material) with respect to the oxygen present and the silicon present. Depending on which is the limiting reagent in the deposition process, the remainder is Si-C and C, SiO2+C reacts to form SiC+C, or SiO2+C reacts incompletely to form Si-O (exiting the device) and Si and SiC. In another embodiment, the starting material or starting pack is formulated as SiC+Si powder+binder to create a shape. This results in a Si-rich starting material.
[0313] Example 9
[0314] A polysilocarb formulation is formulated using a blending type method. The formulation is made by blending 70% MHF, 20% TV, 10% VT at room temperature. The precursor formulation contains 1.17 moles of hydride, 0.23 moles of vinyl, 0.0 moles of phenyl, and 1.53 moles of methyl. The precursor formulation has the following molar amounts of Si, C, and O based on 100 g of formulation: JPEG2025024179000015.jpg49107
[0315] As calculated, the SiOC derived from this formulation has a calculated 0.33 moles of C after all CO is removed, making it 78% C deficient. This material is then pyrolyzed into ceramic and further converted to C-deficient SiC particles and packed.
[0316] Example 10
[0317] Approximately 100 grams of polysilocarb formulation is made. The formulation is blended for 15 minutes at room temperature, then 1% catalyst is added and the mixture is stirred for an additional 10 minutes. The catalyst has 10 ppm Pt in a short chain vinyl terminated polysiloxane.
[0318] The formulation is poured into Teflon (PTFE, polytetrafluoroethylene) coated aluminum foil pans and cured at 90° C. for 2.5 hours in argon or air.
[0319] The cured polymer is mechanically broken into a size that fits into a ceramic boat (e.g., a 3.5 inch long x 2.5 inch wide x 5 / 8 inch deep crucible) and placed into the ceramic boat. The ceramic boat containing the cured polymer is heated in a stainless steel retort filled with argon gas flowing at 500 cc / min as follows: Heat from room temperature to 82.2℃ at a heating rate of 82.2℃ / hr and hold at 82.2℃ for 1 hour. Heating rate of 48.9℃ / hr from 82.2℃ to 182℃, held at 182℃ for 1 hour. Heating rate of 48.9℃ / hr from 182℃ to 210℃, held at 210℃ for 2 hours. Heating rate 115.6℃ / hr from 210℃ to 1,100℃, held at 1,100℃ for 2 hours. · Cool furnace to 204.4°C before opening.
[0320] The pyrolyzed material is placed in a graphite boat in powder or chunk form. The graphite boat is placed in an alumina tube furnace with two end blocks, insulation and caps, to allow gas inflow and waste gas outflow. Argon gas at a flow rate of 50cc / min is flowed through the tube furnace. The material is then heated to 1,650°C over 10 hours (at a heating rate of approximately 3°C / min) and held at this temperature for an additional 10 hours. The furnace is then slowly cooled to 700°C over 5 hours, and the furnace is further cooled until the temperature is at least below 300°C, at which point the end caps are removed.
[0321] The resulting polysilocarb-derived SiC is removed from the furnace.
[0322] The SiC is then formed into a disk by pressing in a cylindrical die at a temperature above the melting temperature of the wax binder that has been melt mixed into the SiC powder. The die can be sized to allow a single monolith of the pressed and sintered powder to be slid into a crucible for PVT growth. The die can also be sized to produce a disk "chip" that pours into the crucible.
[0323] Example 11
[0324] Polysilocarb formulations are made in a cleanroom environment using glassware that has been cleaned to essentially remove all potential impurities, including specifically Al, Fe, and B. The formulation is blended at room temperature for approximately 10-20 hours. Then, 0.25% to 2% catalyst solution is added and the mixture is stirred for an additional 10 minutes. The catalyst solution has 10 ppm Pt, and the final catalyzed formulation has 10-50 ppb Pt.
[0325] In a cleanroom environment, the formulation is placed into a PFA (perfluoroalkoxy polymer) bottle or jar, purged with argon, and capped. The formulation is cured at 75°C to 160°C for 1.5 hours to 4 hours.
[0326] In a clean room environment, the cured polymer is placed into a ceramic crucible. The filled crucible is then covered with a ceramic cap and placed into a ceramic retort filled with argon gas flowing at 500 cc / min. The crucible, furnace and all associated apparatus and equipment are clean and essentially free of contaminants, specifically such that they do not provide a source of Al or B. The crucible is heated at a rate of about 30°C to about 180°C / hr as follows: Room temperature to 1,000°C at a heating rate of 180°C / hr, held at 1,000°C for 2 hours, then · Cool furnace to 204.4°C before opening.
[0327] The pyrolyzed material is placed in a graphite boat, which may be in powder or lump form. The graphite boat is placed in an alumina tube furnace equipped with two end blocks with insulation and caps to allow gas inflow and waste gas outflow. (Graphite box furnaces, RF furnaces, or other types of suitable heating devices may be used.) The crucibles, furnace, and all associated equipment and instruments are clean and essentially free of contamination; in particular, such as not providing a source of Al, Fe, or B. Argon gas is flowed into the tube furnace at a rate of 50 cc / min. The material is then heated (at a heating rate of approximately 3 °C / min) to 1,400-1,650 °C over 7-15 hours and held at this temperature for an additional 10 hours. The furnace is then slowly cooled to 700 °C over 5 hours, and the end caps are removed while the furnace is further cooled to at least 300 °C below the initial temperature.
[0328] The resulting polysilocarb-derived SiC is removed from the furnace.
[0329] Example 12a
[0330] The SiC of Example 11 is then formed into the volume shapes of Examples 13-28 by mixing with 10 wt. % virgin polysilocarb precursor and mixing until uniformly wetted by the resin. The paste is then pressed into a mold using a cold press and die. The shape is removed from the die and placed in a carbon crucible, and the crucible is placed in a graphite furnace and heated to 1750°C for at least 1 hour. The sample is in a manageable shape with a specific gravity of 3.21 g / cc.
[0331] Example 12b
[0332] The SiC of Example 11 is then formed into the volumetric shapes of Examples 13-28 by mixing with 14 wt% virgin polysilocarb precursor and mixing until uniformly wetted with the resin. The paste is then pressed into a mold using a cold press and die. The shape is removed from the die and placed in a carbon crucible, and the crucible is placed in a graphite furnace and heated to 1750°C for at least 1 hour. The sample forms a manageable shape with a specific gravity of 3.21 g / cc.
[0333] Example 12c
[0334] The SiC of Example 11 is then formed into the volumetric shapes of Examples 13-28 by mixing with 20 wt% virgin polysilocarb precursor and mixing until uniformly wetted with the resin. The paste is then pressed into a mold using a cold press and die. The shape is removed from the die and placed in a carbon crucible, and the crucible is placed in a graphite furnace and heated to 1750°C for at least 1 hour. The sample forms a manageable shape with a specific gravity of 3.21 g / cc.
[0335] Example 12d
[0336] The SiC of Example 11 is then formed into the volumetric shapes of Examples 13-28 by mixing with 30 wt. % virgin polysilocarb precursor and mixing until uniformly wetted by the resin. The paste is then pressed into a mold using a cold press and die. The shape is removed from the die and placed into a carbon crucible, and the crucible is placed into a graphite furnace and heated to 1750°C for at least 1 hour. The sample is a manageable shape with a specific gravity of 3.21 g / cc.
[0337] Example 13
[0338] 1A through 1D, a volumetric shape is shown in the form of a cylinder 1 having a flat top 2, sides 3, and a flat bottom. In this embodiment, the shape has a height of about 4 inches and a diameter of about 6 inches. Other sizes of this shape are contemplated, including, for example, heights of about 1 to 6 inches and diameters of about 2 to 12 inches, as well as heights of about 1 / 2 to about 7 inches and diameters of about 1 / 2 to about 17 inches.
[0339] Example 14
[0340] In Figures 2A-2D, a cylindrical volume shape 200 is provided having a flat bottom 203 and an annular hole 204 at the top 201. The annular opening 204 is at the bottom and does not pass completely through the volume shape 200. The volume shape 200 has a side 202. The shape has a height of about 3 inches and a diameter of 4 inches. The diameter of the annular opening is about 1.5 inches. In Figure 2D, a cross-sectional view of this type of shape is shown. It is understood that the schematic is rotated about axis 200 to provide a 3-D shape. Other sizes of this shape are also contemplated, including, for example, heights of about 1 to 6 inches and diameters of about 2 to 12 inches, and heights of about ½ to 7 inches and diameters of about ½ to about 17 inches.
[0341] Example 15
[0342] In Figures 3A-3F, a cylindrical volumetric shape is shown having a spherical opening 303 formed in the top 301 and a spherical opening 305 formed in the bottom 304. The shape has sides 302. It has a height of 4 inches, a diameter of about 4 3 / 4 inches, and a diameter of the opening of about 3 3 / 4 inches. In Figure 3F, a cross-sectional schematic of this type of shape is provided. It is understood that the schematic can be rotated about axis 300 to provide a 3-D shape. Other sizes of this shape are contemplated, including, for example, heights of about 1 to 6 inches and diameters of about 2 to 12 inches, and heights of about 1 / 2 to about 7 inches and diameters of about 1 / 2 to about 17 inches.
[0343] In this embodiment (and other embodiments), the opening is coaxial with the axis, it being understood that the opening may be off-axis, e.g., not on the same axis as the axis of the volumetric feature.
[0344] Example 16
[0345] 4A-4F show a conical volume shape having a flat top 410 and a flat bottom 413. The top 410 has an angled annular opening 414 or channel formed therein. The volume shape has sides 412. The top has a diameter of about 4 1 / 8 inches and the bottom has a diameter of about 4 3 / 8 inches. The height is about 2.5 inches. The annular channel has an opening width of about ½ inch and extends downwards about 1 inch. In FIG. 4F, a cross-sectional schematic of this type of shape 400 is shown. It is understood that this schematic is rotated about axis 401 to provide a three-dimensional shape. The angled annular channel has a length indicated by double arrow 410 and a width indicated by double arrow 411. The angle 405 of the annular channel 414 is determined by the angle formed between line 402 (the centerline of the cross-section of the channel) and axis 401. This angle 405 in Figure 4F is 60°, and in embodiments, ranges from about 89° to about 0°, preferably from about 80° to about 40°, including combinations and variations thereof, and all other sizes of this shape. For example, it is contemplated to include from about 1 to 6 inches in height and about 2 to 12 inches in diameter, and from about ½ to 7 inches in height and ½ to about 17 inches in diameter, combinations and variations thereof, and all values within these dimensional ranges.
[0346] Example 17
[0347] In Figures 5A to 5F, a cone shape is shown having a flat top 501 and a flat bottom 503, the top 501 and bottom 503 having openings 502, 504. The shape has sides 505, such as side walls or sides or outer sides. The openings can be spherical (as shown in Figure 5F), conical with a flat bottom (as shown in Figures 5A to 5E), or cone-shaped. The top has a diameter of about 3.5 inches and the bottom has a diameter of about 5 inches. The side walls have a length of about 27 / 8 inches. In Figure 5F, a cross-sectional schematic of this type of shape is shown. It is understood that the schematic can be rotated about axis 500 to provide a 3-D shape. Other sizes of this shape are also contemplated, including, for example, heights of about 1 to 6 inches and diameters of about 2 to 12 inches, and heights of about 1 / 2 to 7 inches and diameters of about 1 / 2 to about 17 inches.
[0348] Example 18
[0349] In Figures 6A-6D, a conical shape is shown having a flat top 601 and a flat bottom 603, where the bottom 603 has an opening 604. The shape has sides 607. The opening 604 has conical sidewalls 604a, a flat bottom 604b. In embodiments, the opening can be other shapes. The diameter of the bottom is about 5 1 / 2 inches and the top is about 3 inches. The diameter of the opening is about 2 1 / 8 inches. The height is about 2 3 / 8 inches. In Figure 6D, a cross-sectional schematic of this type of shape is shown. It is understood that the schematic is rotated about axis 600 to provide a 3-D shape. For example, heights of about 1 to 6 inches and diameters of about 2 to 12 inches, heights of about 1 / 2 to 7 inches, diameters of about 1 / 2 to about 17 inches, combinations and variations of these, and other sizes are contemplated, including all values within these size ranges.
[0350] Example 19
[0351] In Figures 20A-20C, a cone shape is shown having a flat top 2001, a flat bottom 2003, and a sidewall 2005. The shape has no surface openings on the top, bottom, or sides. The top diameter is about 3 3 / 4 inches, the bottom diameter is about 4 1 / 4 inches, and the height is 2 1 / 2 inches. Other sizes are contemplated including, for example, about 1 to 6 inches in height and about 2 to 12 inches in diameter, and about 1 / 2 to about 7 inches in height and about 1 / 2 to about 17 inches in diameter.
[0352] Example 20
[0353] In Figure 7, a cross-sectional schematic of a cylindrical shape is shown. The shape has a top 701, sides 705, and a bottom 703. The bottom has an opening 704. It is understood that the schematic can be rotated about an axis 700 to provide a 3D shape. Other sizes are contemplated including, for example, heights from 1 / 2 to 7 inches and diameters from about 1 / 2 to about 17 inches.
[0354] Example 21
[0355] In FIG. 8, a cross-sectional schematic of a cone shape with an opening at the top is shown. The shape has a flat top 801, a flat bottom 803, and a side or outer wall 805. There is an opening 802 at the top 801 that extends down at least 40%, at least 50%, at least 60%, and at least 80% of the height of the shape. The opening 802 has a cylindrical side wall 802a and a circular bottom 802b. It is understood that the schematic can be rotated about an axis 800 to provide a 3-D shape. Other sizes are contemplated, including, for example, heights from ½ to 7 inches and diameters from about ½ to about 17 inches.
[0356] Example 22
[0357] 9 shows a cross-sectional schematic of a cylindrical shape with a central through opening 902. The opening 902 extends from the top to the bottom of the shape. As such, the shape can be considered annular. It is understood that the schematic can be rotated about an axis 900 to provide a 3-D shape. Other sizes are contemplated, including, for example, heights from ½ to 7 inches and diameters from about ½ to about 17 inches.
[0358] Example 23
[0359] In FIG. 10, a cross-sectional schematic of a cone shape with a central through opening is shown. The shape has a flat top surface 1001, a flat bottom surface 1003, and side walls 1002. The shape has a central opening 1005 that extends through the surfaces of the top surface 1001 and the bottom surface 1003. The opening 1005a has side walls 1005a. The opening 1005 does not have a bottom. It is understood that the schematic can be rotated about axis 1000 to provide a 3-D shape. Other sizes are contemplated, including, for example, heights from ½ to 7 inches and diameters from about ½ to about 17 inches.
[0360] Example 24
[0361] In FIG. 11, a cross-sectional schematic of a cylindrical shape with a top opening and a bottom opening is shown. The shape has a top opening 1102 with a conical sidewall 1102a and a circular bottom surface 1102b. The shape has a bottom opening 1103 with a conical sidewall 1103a and a bottom surface 1103b. It is understood that the schematic can be rotated about an axis 1100 to provide a 3-D shape. The bottom surfaces 1103b, 1102b are circular. Other sizes are contemplated including, for example, heights from ½ to 7 inches and diameters from about ½ to about 17 inches.
[0362] Example 25
[0363] 12 shows a cross-sectional schematic of a cone shape with openings at the top 1202 and bottom 1203. It is understood that the schematic can be rotated about axis 1200 to provide a 3-D shape. Other sizes are contemplated including, for example, heights from ½ to 7 inches and diameters from about ½ to about 17 inches.
[0364] Example 26
[0365] 13 shows a cross-sectional schematic of a cylindrical shape with a spherical top opening 1302. The opening 1302 has surface 1302a that forms both the bottom and side walls of the opening. It is understood that the schematic can be rotated about axis 1300 to provide a 3-D shape. Other sizes are contemplated including, for example, heights from ½ to 7 inches and diameters from about ½ to about 17 inches.
[0366] Example 27
[0367] In Figure 14, a cross-sectional schematic of a cone shape with a spherical top opening 1402 is shown. The shape has a top 1401, a side 1405. The spherical top opening 1402 has a surface 1402a which forms both the sidewall and the bottom of the opening 1402. It is understood that the schematic can be rotated about an axis 1400 to provide a 3-D shape. Other sizes are contemplated including, for example, heights from 1 / 2 to 7 inches and diameters from about 1 / 2 to about 17 inches.
[0368] Example 28
[0369] In FIG. 15, a cross-sectional schematic of a cylindrical shape with a top annular opening 1505 is shown. The shape has a sidewall surface 1515 and a top surface or upper surface 1510. The schematic is rotated about axis 1500 to provide a 3-D shape. The angle 1502 of the annular channel 1505 is determined by the angle formed between line 1501 (the centerline of the cross-section of the channel 1505) and axis 1501. In this illustrated embodiment, it is 60°, and can range from about 89° to about 0°, preferably from about 80° to about 40°. Other sizes are also contemplated, including, for example, heights of ½ to about 7 inches and diameters of about ½ to about 17 inches, as well as all values within these size ranges.
[0370] Example 29
[0371] It has a purity of 7-nine and a primary particle size of 0.2 μm. 50The sized granular polymer-derived SiC is forced into a volumetric shape as follows.
[0372] Example 30
[0373] The polysilocarb derived SiC is ground to 0.2 μm and compressed in a cold press into shapes with a binder appropriate for pre-cured strength (i.e., ability to process the shape including press to cure operations). The sample is then placed in a hot isostatic press and heated to 2100 °C in an argon atmosphere at 30,000 psi and held for up to 5 hours, then slowly cooled. The shape can be any of the shapes in Examples 13 to 28.
[0374] Example 30
[0375] It has a purity of 7-nine and a primary particle size of 1.0 μm. 50 The sized particulate polymer-derived SiC is made into any of the shapes of Examples 13-28.
[0376] Example 31
[0377] It has a purity of 7-nine and a primary particle size of 1.5 μm. 50 The sized granular polymer-derived SiC is made into any of the shapes of Examples 13-28.
[0378] Example 32
[0379] The polysilocarb-derived SiC particles, having an average diameter of about 0.4 μm, are essential to be free of an oxide layer on their surface. The SiC particles are formed into any of the shapes of Examples 13-28 using an oxygen-free binder.
[0380] Example 33
[0381] The polysilocarb-derived SiC particles, having an average diameter of about 0.6 μm, are essential to be free of an oxide layer on their surface. The SiC particles are formed into any of the shapes of Examples 13-28 using a binder containing only carbon and hydrogen.
[0382] Example 34
[0383] The polysilocarb-derived SiC particles, having an average diameter of about 0.4-0.6 μm, are essential to be free of an oxide layer on their surface. The SiC particles are formed into any of the shapes of Examples 13-28 using a binder containing hydrogen and carbon but no oxygen.
[0384] Example 35
[0385] The SiC particles are formed using a polysilocarb binder into any of the shapes of Examples 13 to 28. The formed shapes have an elastic modulus of 2 MPa and a compressive strength of 7.47 MPa.
[0386] If greater strength is required, the SiC volume shapes can be subjected to high temperature sintering (such as hot pressing or hot isostatic pressing) prior to use. Such operations tend to provide a less porous structure, e.g., less than 20% porosity.
[0387] Example 36
[0388] The volumetric shapes of any of the shapes of Examples 13-28 are made from 85%-95% polysilocarb-derived SiC powder and 13%-5% 41 / 59MH / TV polysilocarb precursor.
[0389] Example 37
[0390] 99% to 88% polysilocarb derived SiC powder is mixed with 1% to 12% ultra-high purity hydrocarbon wax (or polyethylene or polymer or oil with only C or H atoms). This mixture is melted and mixed before being pressed into a pill, any of the shapes of Examples 13-28, or other volumetric shapes.
[0391] Example 38
[0392] 100%-95% polysilocarb derived SiC powder is mixed with 0%-5% ultra-high purity hydrocarbon binder and pressed using spark plasma sintering to obtain SiC volume shapes of any of the shapes in Examples 13-28, with the partially sintered cases having an excess carbon content of 0-5%.
[0393] Example 40
[0394] The volume shapes of Examples 13-38 are used in a deposition apparatus to grow boules of single crystal SiC. The boules can be 3 inches, 4 inches, 6 inches, 8 inches or larger, and all values within these size ranges.
[0395] The deposition process for the growth of a 3 inch boule is outlined as follows: 1. Cleaning graphite parts and insulation: Vacuum at a minimum of 1000°C for at least 3 hours. 2.Heating: 2100-2250°C at the top of the crucible, 500-700 torr pressure, Gas flow rate: 100sccmAr; Heat for 10 hours; for example, to reach a temperature of 2130-2145°C. Reduce the temperature to 2073°C 3. Begin the growth cycle. Reduce the pressure to the desired growth pressure (0.1-50 Torr) to initiate sublimation and growth. The pressure is then reduced to 15 Torr. 4.Growth cycle: Grown at 2145℃ (measurement point at the top of the crucible) 5. End of growth cycle Backfill the reaction chamber with 500-700 torr argon 6. Cool Down Cools to near ambient temperature in 40 hours
[0396] The growth cycle time was 73 hours, the growth rate averaged 360 μm / h, and the boule height was 26.8 mm. Approximately 67% of the feedstock was consumed, with 204 g remaining from 610 g of starting material.
[0397] Example 40a
[0398] The boule of Example 40 is cut into wafers using wafer cutting equipment such as diamond wire saws, multi-wire diamond saws, slurry wire saws, blade diamond cut-off saws, or other cutting equipment with larger kerf losses, or other equipment with smaller kerf losses, such as optical laser slicing as reported by Disco Tech (KABRA technology, see www.discousa.com). Wafers can also be cut with a Takatori multi-wire saw sold in the United States under the brand name GTI TECHNOLODIES. The cut wafers can be ground using a grinder if desired. For example, suitable grinders are offered by REVASUM, see www.revasum.com.
[0399] Example 40b
[0400] The wafer of Example 40a is polished on one side, preferably on both sides. For example, polishing equipment includes chemical mechanical polishing (CMP), lapping, grinding, slurry polishing, and dry polishing. For example, a suitable polisher is provided by GigaMat Technologies (see, for example, www.gigamat.com).
[0401] Example 40c
[0402] The wafers of Example 40b have circuits printed thereon (e.g., by epitaxy or semiconductor wafer processing) to form electronic components, e.g., circuits, circuits, integrated circuits. For a 6-inch wafer, about 300-5000 individual components can be formed. The method and resulting wafers provide about 3-4 times more usable components, i.e., usable devices, than can be formed from current wafers made from current starting materials and processes (i.e., wafers and processes prior to the present invention). For example, about 20% to 60%, about 20% to about 50%, about 20% or more of the devices made from current wafers are unusable. The devices made from the wafers of the present invention are capable of working about 80% to 100% of these devices, about 80% or more of these devices, about 90% or more, about 95% or more, about 99% or more.
[0403] Example 40d
[0404] The electronic components of example 40c are assembled into an electronic module. The module can include from a few, e.g., 1-10, electronic components to about 100 to about 1000 electronic components. The module can be, for example, power transformer units, metal oxide semiconductor field effect transistors (MOSFETs), junction field effect transistors (JFETs), insulated gate bipolar transistors (IGBTs), and bipolar junction transistors (BJTs).
[0405] Example 40e
[0406] The modules of example 40d are assembled into a power block. Approximately 1 to 100 modules can be used in a power block.
[0407] Example 40f
[0408] The module of example 40d or the power block of example 40e may be assembled into systems such as solar inverters, wind converters, hybrid cars, data centers, and medical imaging devices such as MRI.
[0409] Example 40g
[0410] The process of Example 40 has starting material with purity of 6-99%, has directional flux channels in the volumetric geometry, and consumes 80% of the starting material during the growth cycle.
[0411] Example 40h
[0412] The process of Example 40 has starting material with purity of 6-9%, has directional flux channels in the volumetric geometry, and consumes 90% of the starting material during the growth cycle.
[0413] Example 40i
[0414] The process of Example 40 has starting material with purity of 6-99%, has directional flux channels in the volumetric geometry, and consumes 95% of the starting material during the growth cycle.
[0415] Example 41
[0416] The wafers of Example 40a have the characteristics of Dow Corning Prime Ultra SiC wafers. The 100 mm wafers have MPD (≦0.1 cm-2), TSD (≦300 cm-2), and BPD (≦500 cm-2). The 150 mm wafers have MPD (<1 cm-2), TSD (≦200 cm-2), and BPD (≦3,000 cm-2).
[0417] Example 42
[0418] The wafer of Example 40a has the following characteristics: 150 mm wafer has MPD (≦0.1 cm−2), TSD (≦300 cm−2) and BPD (≦500 cm−2).
[0419] Example 43
[0420] The wafer of Example 40a has a resistivity of greater than about 10,000 ohm-cm at 20°C.
[0421] For the above examples, it will be understood that in preferred embodiments, the openings are in the top, bottom, or both, and these openings are coaxial with the axis of the shape, and the openings are each of the same general type, e.g., both the top and bottom are spherical. As will be understood, in embodiments, the openings may be in the side walls, which may be the same or different than the top, bottom, or side walls. The openings may be coaxial or off-axis with respect to the axis of the shape. Overview - Polysilocarb Formulations, Methods, and Materials
[0422] Various polysilocarb formulations, processes, methods of manufacture, and formulations are taught and disclosed in U.S. Patent Nos. 9,499,677, 9,481,781 and U.S. Patent Publication Nos. 2014 / 0274658, 2014 / 0323364, 2015 / 0175750, 2016 / 0207782, 2016 / 0280607, and 2017 / 0050337, the entire disclosures of each of which are incorporated herein by reference. General process for obtaining polysilocarb precursors
[0423] Typically, polymer-derived ceramic precursor formulations, particularly polysilocarb precursor formulations, can be made by three general types of processes, although other processes, and variations and combinations of these processes may be utilized. These processes generally include combining precursors to form a precursor formulation. One type of process generally includes mixing precursor materials, preferably in a solvent-free process where essentially no chemical reaction occurs, such as, for example, a "mixing process." Another type of process generally includes chemical reactions, such as, for example, "reaction type," to form a particular precursor formulation, which may be, for example, monomers, dimers, trimers, and polymers. A third type of process has chemical reactions of two or more components in a solvent-free environment, such as, for example, a "reaction mixing type process." Generally, in a mixing process, essentially all, and preferably all, of the chemical reactions take place during subsequent processing, such as during curing, pyrolysis, and the like.
[0424] It is understood that these terms (reactive process, reactive mixed process, and mixed process) are used for convenience and as a shorthand reference. These terms, i.e., process types, are not and should not be considered limiting. For example, a precursor material can be made using a reactive process and then used in a mixed process with another precursor material.
[0425] These process types are described herein under respective headings. It should be understood that the teachings of one process under one heading and the teachings of other processes under other headings are applicable to each other and to other sections, embodiments and teachings of this section. Starting materials or precursors of one type of process may be used in other types of processes. Moreover, the processes described under these headings should be read in conjunction with the entirety of this specification, including the various examples and embodiments.
[0426] It is understood that combinations and variations of these processes can be used in arriving at precursor formulations, and in arriving at intermediate, final, and end products. Depending on the particular process and desired characteristics of the product, precursors and starting materials from one process type can be used in other process types. Formulations from a mixed type process can be used as precursors, or components, in a reactive mixed type process, or in a reactive mixed type process. Similarly, formulations from a reactive type process can be used in mixed type processes and reactive mixed processes. Similarly, formulations from a reactive mixed type process can be used in mixed type processes and reactive mixed processes. Thus, and preferably, optimal performance and features from other processes can be combined and utilized to provide cost-effective and efficient processes and end products. Any of these processes, and combinations thereof, can provide a particular given product, as these processes offer great flexibility to create custom features of intermediate, final, and end products. Factors such as cost, controllability, shelf life, scale-up, ease of manufacture, etc. can be considered in selecting which type of process is preferred.
[0427] The precursor formulations may be used to form "neat" materials ("neat" materials means all, and essentially all, of the structure made from the precursor material or formulation that is unfilled; thus, for example, there are no fillers or reinforcements). The precursor formulations may be used to form, for example, filled materials having additives or other materials in addition to the precursor. They may be used to form composite materials, for example, structures or coatings that include other materials, such as reinforcements. They may be used to form non-reinforced materials, which are materials that are primarily, essentially, and preferably only made from the precursor material, for example, minimally filled materials where the fillers are not intended to add or enhance strength, and non-filled materials. They are suitable for forming reinforced materials, such as materials with fibers or other materials to add strength, wear resistance, durability, or other features or characteristics, generally considered to be strength-related in the broad sense.
[0428] In general, types of filler materials include inert fillers, such as inorganic materials that do not react with the SiOC matrix during curing, pyrolysis, or use; reactive fillers, such as zirconium, aluminum hydroxide, boron compounds, etc., that react with the SiOC matrix during curing, pyrolysis, use, or a combination thereof; and active fillers, such as materials that are released during use of the final product to provide a specific function to the product, e.g., lubricants. Fillers may be classified into more than one of these types.
[0429] The filler material may be made from or derived from the same material as the formulation that has been formed into a cured or pyrolyzed solid, or may be made from a different precursor formulation material that has been cured into a solid or semi-solid, or pyrolyzed solid.
[0430] Polysilocarb formulations and products derived or manufactured from them can have metals and metal complexes.Thus, metals as oxides, carbides, or silicides can be introduced into the precursor formulation and thus into the silica matrix in a controlled manner.For example, organometallics, metal halides (chlorides, bromides, iodides), metal alkoxides, and metal amide compounds of transition metals can be copolymerized in the silica matrix by being incorporated into the precursor formulation.
[0431] Fillers can impart, adjust, or enhance, for example, functions and properties such as electrical resistivity, magnetic ability, band gap functionality, pn junction functionality, p-type functionality, n-type functionality, dopants, electrical conductivity, semiconductors, antistatic, optical properties (reflectance, refractive index, iridescence, etc.), chemical resistivity, corrosion resistance, abrasion resistance, wear resistance, thermal insulation, UV stability, UV protection, and other desirable and required properties, and / or characteristics, in the final product or material.
[0432] Thus, filler materials include copper leads, thermally conductive fillers, electrically conductive fillers, lead, optical fibers, ceramic colorants, pigments, oxides, dyes, powders, ceramic fines, polymer-derived ceramic particles, pore formers, carbosilanes, silanes, silazanes, silicon carbide, carbosilazanes, siloxanes, metal powders, ceramic powders, metals, metal complexes, carbon, tows, fibers, short fibers, boron-containing materials, ground fibers, glass, glass fibers, glass fibers, and nanostructures (the aforementioned nanostructures, to name a few). For example, ground polymer-derived ceramic particles, such as fines or beads, can be added to a polysilocarb formulation and then cured to form a filled, cured plastic material that has the remarkable property of fire resistance as a coating or as a device or device component.
[0433] The polysilocarb precursor formulations can be used with reinforcing materials to form composite layers or coatings. Thus, for example, the formulations can be cast, impregnated, imbibed, or otherwise combined with thin reinforcing materials such as carbon fiber, glass fiber, woven fabrics, nonwoven fabrics, copped fibers, fibers, ropes, retinal structures, ceramic powders, glass powders, carbon powders, graphite powders, ceramic fibers, metal powders, carbide pellets or components, staple fibers, tows, the above nanostructures, PDC, other materials that meet the temperature requirements of the process and final product, and combinations and variations thereof. Thus, for example, the reinforcing materials can be any of the high temperature resistant reinforcing materials currently used or that can be used with existing plastic and ceramic composites. Additionally, polysilocarb precursor formulations can be formulated for low temperature cure (such as SATP) or cure temperatures from about 100°F to about 400°F, so the reinforcing materials can be reinforcing polymers, organic polymers such as nylon, polypropylene, polyethylene, and aramid fibers such as NOMEX and KEVLAR®.
[0434] The reinforcing material may also be made from or derived from the same materials as the composition that is formed into fibers, cured to a solid, and pyrolyzed to a ceramic, or may be made from different precursor composition materials that are formed into fibers and pyrolyzed to a ceramic, combinations and variations thereof. In addition to ceramic fibers derived from the precursor composition materials that may be used as reinforcing materials, other porous, substantially porous, and non-porous ceramic structures derived from the precursor composition materials may be used.
[0435] Polysilocarb materials (e.g., precursor batches, precursors, formulations, bulk liquids, etc.) may have various inhibitors, catalysts, and initiators present that inhibit, modulate, or promote curing under certain conditions. Thus, polysilocarb coating materials may have sufficient inhibitors present or no catalysts present to provide the necessary shelf life for the material during storage. Mixed-type processes
[0436] The precursor materials can be methylhydrogens (methyl terminated hydride substituted polysiloxanes), methylhydrogen fluids (methyl terminated hydride methyl substituted polysiloxanes, with few or no dimethyl groups) and substituted and modified methylhydrogens, siloxane backbone materials, siloxane backbone additives, reactive monomers, reaction products of siloxane backbone additives with silane or organic modifiers, and other similar types of materials such as silane-based materials, silazane-based materials, carbosilane-based materials, non-silicon organic crosslinkers, phenolic / formaldehyde-based materials, and combinations and variations thereof. The precursors are preferably liquids at room temperature, but they may melt or be solids that are soluble in one of the other precursors. (However, it should be understood that in this context, one precursor is not considered a "solvent" even if it dissolves another precursor, as that term is used in reference to prior art processes that use non-constituent solvents, e.g., solvents that do not form part of the constituents of the final product and are treated as waste.)
[0437] The precursors are mixed together in a container, preferably at room temperature. Preferably, little, more preferably no, solvents, e.g., water, organic solvents, polar solvents, non-polar solvents, hexane, THF, toluene, are added to this mixture of precursor materials. Preferably, each precursor material is miscible with the others, e.g., they can be mixed in any relative amount or in any proportion, and do not separate or precipitate. In this respect, the "precursor mixture" or "polysilocarbo precursor formulation" is complete (if only a single precursor is used, the material would not simply be a "polysilocarbo precursor" or "polysilocarbo precursor formulation" or "formulation"). Although complete, fillers and reinforcing agents can be added to the formulation. In a preferred embodiment of the formulation, essentially no, more preferably no, chemical reaction, e.g., crosslinking or polymerization, occurs within the formulation when it is mixed or when the formulation before curing is held in the container.
[0438] The precursors can be mixed under many different atmospheres and conditions, for example, air, inert gas, N2, argon, flowing gas, static gas, reduced pressure, elevated pressure, atmospheric pressure, and combinations and variations thereof.
[0439] Additionally, inhibitors such as cyclohexane, 1-ethynyl-1-cyclohexanol (available from ALDRICH), octamethylcyclotetrasiloxane (which can be considered a diluent), and tetramethyltetravinylcyclotetrasiloxane can be added to the polysilocarb precursor formulation, for example, to form an inhibited polysilocarb precursor formulation. It should be noted that tetramethyltetravinylcyclotetrasiloxane can act as both a reactant and a reaction retarder (e.g., an inhibitor) depending on the amount present and the temperature, e.g., at room temperature it is a retarder and at elevated temperatures it is a reactant. At this point in the process, fillers such as SiC powder, carbon black, sand, polymer-derived ceramic particles, pigments, particles, nanotubes, whiskers, or other materials discussed herein or otherwise known in the art can also be added to the polysilocarb precursor formulation, e.g., a filled polysilocarb precursor formulation. Additionally, a formulation that includes both an inhibitor and a filler is considered an inhibited and filled polysilocarb precursor formulation.
[0440] A catalyst or initiator may be used and may be added before, just before, or at an earlier point before the precursor formulation is formed or structured prior to curing. Catalysis promotes and aids in the curing of the precursor formulation to form a cured material or structure.
[0441] The catalyst can be any platinum (Pt) based catalyst that can be diluted to a range of, for example, about 0.01 ppm Pt to about 250 ppm Pt, about 0.03 ppm Pt, about 0.1 ppm Pt, about 0.2 ppm Pt, about 0.5 ppm Pt, about 0.02 to 0.5 ppm Pt, about 1 ppm to 200 ppm Pt, and preferably, in some applications and embodiments, about 5 ppm to 50 ppm Pt. The catalyst can be, for example, a peroxide-based catalyst with a 10 hour half-life above 90° C. at a concentration of 0.1% to 3% peroxide, and about 0.5% to 2% peroxide. It can be an organic-based peroxide. This is any organometallic catalyst capable of reacting with Si-H bonds, Si-OH bonds, or unsaturated carbon bonds; these catalysts include organometallic compounds such as dibutyltin dilaurate, zinc octoate, peroxide, titanium, zirconium, rhodium, iridium, palladium, cobalt, or nickel. The catalyst may be other rhodium, rhenium, iridium, palladium, nickel, and ruthenium type or based catalysts. Combinations and variations of these and other catalysts may be used. Catalysts are available from ARKEMA under the trade name LUPEROX (e.g. LUPEROX 231; from Johnson Matthey, they are sold under the trade names Karstedt's catalyst, Ashby's catalyst, and Speier's catalyst. Transition metal catalysts such as Fe catalyst, Ni catalyst, and Co catalyst, which are used for example in the growth of regular and highly ordered carbon structures such as carbon nanotubes, may also be used.
[0442] Additionally, custom and specific combinations of these and other catalysts can be used to match specific formulations, thus selectively and specifically catalyzing the reactions of specific components. Additionally, the use of these types of matched catalyst formulation systems, as well as process conditions, can be used to achieve a wide variety of applications, including, for example, pore structure, porosity, density, density profile, high purity, ultra-high purity, and high yield. Other forms or characteristics of the hardened structure or material, and in some cases, can be used to provide a predetermined product function, such as a ceramic formed from the hardened structure or material.
[0443] In this mixed type process for making the precursor formulation, preferably chemical reactions or molecular rearrangements occur only during the preparation of the raw starting materials, during the curing process, and during the pyrolysis process. Preferably, in these mixed type formulation and process embodiments, polymerization, crosslinking or other chemical reactions occur primarily, preferably essentially, and more preferably only during the curing process.
[0444] The precursor may be a methyl terminated hydride substituted polysiloxane, which may be referred to herein as methyl hydrogen (MH), having the formula shown below. JPEG2025024179000016.jpg4085
[0445] The MH may have, for example, a molecular weight of about 400 mw to about 10,000 mw, about 600 mw to about 3,000 mw ("mw" can be measured as weight average molecular weight in atomic mass units, amu, or g / mol), and preferably a viscosity of about 20 cps to about 60 cps. The percentage of methylsiloxane units "X" may be 1% to 100%. The percentage of dimethylsiloxane units "Y" may be 0% to 99%. This precursor may be used to provide the backbone of the crosslinked structure, as well as other characteristics and properties to the cured preform and ceramic material. This precursor may be modified, inter alia, by reacting with unsaturated carbon compounds to produce new or additional precursors. Typically, the minimum amount of methylhydrogen fluid (MHF) is "Y", and more preferably "Y" is zero for all practical purposes.
[0446] The precursor can be any of the following linear siloxane backbone materials:
[0447] The precursor may be a vinyl substituted polydimethylsiloxane, the formula of which is shown below: JPEG2025024179000017.jpg3983
[0448] The precursor may have, for example, a molecular weight (mw) of about 400 mw to about 10,000 mw, and preferably a viscosity of about 50 cps to about 2,000 cps. The percentage of methylvinylsiloxane units "X" may be 1% to 100%. The percentage of dimethylsiloxane units "Y" may be 0% to 99%. Preferably, X is about 100%. The precursor may be used to increase crosslink density and improve toughness and other characteristics and properties of the cured preform and ceramic material.
[0449] The precursor may be a vinyl substituted and vinyl terminated polydimethylsiloxane, the formula of which is shown below. JPEG2025024179000018.jpg3990
[0450] The precursor may have, for example, a molecular weight (mw) of about 500 mw to about 15,000 mw, preferably about 500 mw to 1,000 mw, and a viscosity of preferably about 10 cps to about 200 cps. The percentage of methylvinylsiloxane units "X" may be 1% to 100%. The percentage of dimethylsiloxane units "Y" may be 0% to 99%. The precursor may be used to provide branching, reduce curing temperatures, and other characteristics and properties of the cured preform and ceramic materials.
[0451] The precursor may be a vinyl-substituted and hydrogen-terminated polydimethylsiloxane, the formula of which is shown below. JPEG2025024179000019.jpg3890
[0452] The precursor may have a molecular weight (mw) of about 300 mw to about 10,000 mw, preferably a molecular weight of about 400 mw to 800 mw, and preferably a viscosity of about 20 cps to about 300 cps. The percentage of methylvinylsiloxane units "X" may be 1% to 100%. The percentage of dimethylsiloxane units "Y" may be 0% to 99%. This precursor may be used to provide branching, reduce curing temperatures, and other characteristics and properties of the cured preform and ceramic material.
[0453] The precursor may be an allyl-terminated polydimethylsiloxane, the formula of which is shown below: JPEG2025024179000020.jpg38103
[0454] The precursor may have a molecular weight (mw) of about 400 mw to about 10,000 mw, and preferably a viscosity of about 40 cps to about 400 cps. The repeating units are the same. The precursor can be used to provide UV curability, extend polymer chains, and impart other features and properties to the cured preform and ceramic materials.
[0455] The precursor may be vinyl-terminated polydimethylsiloxane (VT), the formula of which is shown below: JPEG2025024179000021.jpg3886
[0456] The precursor may have a molecular weight (mw) of about 200 mw to about 5,000 mw, preferably a molecular weight of about 400 mw to 1500 mw, and may have a viscosity of preferably about 10 cps to about 400 cps. The repeating units are the same. The precursor may be used to provide polymer chain extenders, improve toughness, reduce cure temperatures, for example to room temperature cure, and other characteristics and properties of the cured preform and ceramic material.
[0457] The precursor may be a silanol (hydroxy) terminated polydimethylsiloxane, the formula of which is shown below. JPEG2025024179000022.jpg3981
[0458] The precursor may have a molecular weight (mw) of about 400 mw to about 10,000 mw, preferably a molecular weight of about 600 mw to 1,000 mw, and preferably a viscosity of about 30 cps to about 400 cps. The repeating units are the same. The precursor can be used to provide polymer chain extenders, reinforcement mechanisms, can produce nano- and micro-scale porosity, allows for curing at room temperature, and other features and properties of the cured preform and ceramic material.
[0459] The precursor may be a silanol (hydroxy) terminated vinyl substituted dimethylsiloxane, the formula of which is shown below. JPEG2025024179000023.jpg4186
[0460] The precursor may have a molecular weight (mw) of about 400 mw to about 10,000 mw, preferably about 600 mw to 1,000 mw, and preferably a viscosity of about 30 cps to about 400 cps. The percentage of methylvinylsiloxane units "X" may be 1% to 100%. The percentage of dimethylsiloxane units "Y" may be 0% to 99%. The precursor may be used in particular in dual cure systems. In this way, the dual cure allows the use of multiple curing mechanisms in a single formulation. For example, both condensation and addition cures can be utilized. This allows complex cure profiles to be obtained, for example, initial cure with one type of cure and final cure with another type of cure.
[0461] The precursor may be a hydrogen (hydride) terminated polydimethylsiloxane, the formula of which is shown below: JPEG2025024179000024.jpg3882
[0462] The precursor may have a molecular weight (mw) of about 200 mw to about 10,000 mw, preferably a molecular weight of about 500 mw to 1500 mw, and preferably a viscosity of about 20 cps to about 400 cps. The repeating units are the same. The precursor may be used to provide polymer chain extenders as toughening agents, allowing for curing such as low temperature, cured preforms, and other characteristics and properties of the ceramic material.
[0463] The precursor can be a diphenyl-terminated siloxane (also called phenyl-terminated), the formula of which is shown below: JPEG2025024179000025.jpg4394
[0464] where R is a reactive group such as vinyl, hydroxy, or hydride. The precursor may have a molecular weight (mw) of about 500 mw to about 2,000 mw, and preferably a viscosity of about 80 cps to about 300 cps. The percentage of methyl-R-siloxane units "X" may be 1% to 100%. The percentage of dimethylsiloxane units "Y" may be 0% to 99%. The precursor may be used to provide reinforcement, adjust the refractive index of the polymer to match that of various types of glass, for example, to provide transparent glass fibers, and other features and properties to the cured preforms and ceramic materials.
[0465] The precursor can be a monophenyl-terminated siloxane (also called a trimethyl-terminated, phenyl-terminated siloxane), the formula of which is shown below: JPEG2025024179000026.jpg4290
[0466] where R is a reactive group such as vinyl, hydroxy, or hydride. The precursor may have a molecular weight (mw) of about 500 mw to about 2,000 mw, and preferably a viscosity of about 80 cps to about 300 cps. The percentage of methyl-R-siloxane units "X" may be 1% to 100%, and the percentage of dimethylsiloxane units "Y" may be 0% to 99%. The precursor is used to provide reinforcement, adjust the refractive index of the polymer to match that of various types of glass, and provide other features and properties, for example, in transparent glass fibers, cured preforms, and ceramic materials.
[0467] The precursor may be diphenyldimethylpolysiloxane, the formula of which is shown below: JPEG2025024179000027.jpg3879
[0468] The precursor may have a molecular weight (mw) of about 500 mw to about 20,000 mw, may have a molecular weight of about 800 to about 4,000, and may preferably have a viscosity of about 100 cps to about 800 cps. The percentage of dimethylsiloxane units "X" may be 25% to 95%. The percentage of diphenylsiloxane units "Y" may be 5% to 75%. This precursor may be used to provide similar properties to monophenyl-terminated siloxanes, as well as other features and properties to the cured preform and ceramic materials.
[0469] The precursor may be a vinyl terminated diphenyldimethylpolysiloxane, the formula of which is shown below. JPEG2025024179000028.jpg3691
[0470] The precursor may have a molecular weight (mw) of about 400 mw to about 20,000 mw, may have a molecular weight of about 800 to about 2,000 mw, and may preferably have a viscosity of about 80 cps to about 600 cps. The percentage of dimethylsiloxane units "X" may be 25% to 95%. The percentage of diphenylsiloxane units "Y" may be 5% to 75%. The precursor may be used to provide chain extension, toughening, refractive index modification or alteration, improved high temperature thermal stability of the cured material, and other features and properties of the cured preform and ceramic material.
[0471] The precursor may be a hydroxy-terminated diphenyldimethylpolysiloxane, the formula of which is shown below: JPEG2025024179000029.jpg4286
[0472] The precursor may have a molecular weight (mw) of about 400 mw to about 20,000 mw, may have a molecular weight of about 800 to about 2,000 mw, and may preferably have a viscosity of about 80 cps to about 400 cps. The percentage of dimethylsiloxane units "X" may be 25% to 95%. The percentage of diphenylsiloxane units "Y" may be 5% to 75%. The precursor may be used for chain extension, toughening, refractive index modification or alteration, improving high temperature thermal stability of the cured material, producing nanoscale and microscale porosity, as well as producing other functions and properties in the cured preform and ceramic material.
[0473] This precursor may be a methyl-terminated phenylethylpolysiloxane (also called styrene vinylbenzene dimethylpolysiloxane), the formula of which is shown below: JPEG2025024179000030.jpg4185
[0474] The precursor may have a molecular weight (mw) of about 800 mw to at least about 10,000 mw to at least about 20,000 mw and a viscosity of preferably about 50 cps to about 350 cps. The percentage of styrene vinyl benzene siloxane units "X" may be 1% to 60%. The percentage of dimethyl siloxane units "Y" may be 40% to 99%. The precursor may be used to improve toughness, reduce reaction cure exotherms, modify the refractive index, adjust the refractive index of the polymer to match that of various types of glass, for example to provide transparent fiberglass, and to provide other features and properties to the cured preform and ceramic materials.
[0475] It will be understood that the linear siloxane backbone materials described above are by way of example only and that other similar linear siloxane backbone materials can also be used as precursors. More complex linear and branched siloxane backbone materials may also be used as precursors, but are not preferred.
[0476] Various cyclosiloxanes can be used as precursors, which are the reactive molecules in the formulation. They can be described by the following naming system or formula: DxD* y, where "D" represents a dimethylsiloxy unit, "D*" represents a substituted methylsiloxy unit, the "*" group is vinyl, allyl, hydrido, hydroxy, phenyl, styryl, alkyl, cyclopentadienyl, or other organic groups, x is 0-8, y is >=1, and x+y is 3-8. Furthermore, in this naming system, D represents a -SiO2 group, usually Me2SiO2, Q represents SiO4, T represents a -SiO3 group, usually MeSiO3, and M represents a -SiO group, usually Me3SiO.
[0477] The precursor batch may also include non-silicon-based precursors, such as (i) non-silicon-based crosslinkers, (ii) reaction products of non-silicon-based crosslinkers and silicon-based precursors, and (iii) combinations and variations thereof. The non-silicon-based crosslinkers are intended to provide the ability to crosslink during curing. For example, non-silicon-based crosslinkers include cyclopentadiene (CP), methylcyclopentadiene (MeCP), dicyclopentadiene (DCPD), methyldicyclopentadiene (MeDCPD), tricyclopentadiene (TCPD), piperylene, divinylbenzene, isoprene, norbornadiene, vinylnorbornene, propenylnorbornene, isopropenylnorbornene, methylvinylnorbornene, bicyclononadiene, methylbicyclononadiene, propadiene, 4-vinylcyclohexene, 1,3-heptadiene, cycloheptadiene, 1,3-butadiene, cyclooctadiene, and isomers thereof. In general, any hydrocarbon containing two (or more) C=C bonds that react with Si-H or other Si bonds in the precursor can be used as a crosslinker. Some organic materials that contain oxygen, nitrogen, or sulfur can also function as crosslinkers.
[0478] The amount of non-silicon based crosslinker relative to the silicon based precursor can be from about 10% to 90% non-silicon based crosslinker to 10% to 90% silicon based precursor (preferably silicon backbone). (e.g. -Si-O- backbone, material). Thus, the amount ranges, for example, 10 / 90 to 90 / 10 DCPD / MHF, about 40 / 60 to 60 / 40, about 50 / 50, and combinations and variations of these ratios, as well as other ratios. Third and fourth precursor materials can also be used. Thus, the ratio of non-silicon crosslinker / silicon backbone precursor / third precursor can be: from about 10% to about 80% non-silicon based crosslinker; from about 10% to 80% silicon based precursor; and from about 0.1% to 40% third precursor. The ranges and amounts of DCPD / MHF / third precursor can be, for example, about 10 / 20 / 70 to 70 / 20 / 10, about 10 / 20 / 70 to 10 / 70 / 20, about 45 / 55 / 10 to about 55 / 45 / 10, about 40 / 55 / 5 to about 55 / 40 / 5, and combinations and variations of these and other ratios.
[0479] The precursors may be reactive monomers. These include molecules such as tetramethyltetravinylcyclotetrasiloxane (TV), the formula of which is shown below: JPEG2025024179000031.jpg4748
[0480] This precursor can be used to provide branching agents, three-dimensional crosslinkers, and other features and properties to the cured preform and ceramic materials. (It should also be noted that in certain formulations, such as 2% or more, and at certain temperatures, such as from about room temperature to about 60° C., this precursor may inhibit crosslinking, e.g., inhibiting the crosslinking of hydrides with vinyl groups.)
[0481] The precursor may be a reactive monomer, such as, for example, trivinylcyclotetrasiloxane. JPEG2025024179000032.jpg5054
[0482] Divinylcyclotetrasiloxane, JPEG2025024179000033.jpg4943
[0483] Trivinyl monohydride cyclotetrasiloxane JPEG2025024179000034.jpg4952
[0484] Divinyldihydridocyclotetrasiloxane JPEG2025024179000035.jpg5745
[0485] and hexamethylcyclotetrasiloxane, e.g. JPEG2025024179000036.jpg41104
[0486] The precursors may be silane modifiers such as vinylphenylmethylsilane, diphenylsilane, diphenylmethylsilane, and phenylmethylsilane (some of which may be used as end-capping or end-terminating groups). These silane modifiers can provide chain extenders and branching agents. They also improve the strength of the cured material, as well as improve the toughness of the cured material, modify the refractive index, and improve the high temperature cure stability, among other things. Precursors such as diphenylmethylsilane act as end-capping agents, improve the toughness, modify the refractive index, improve the high temperature cure stability of the cured material, and improve the strength of the cured material.
[0487] The precursor may be a reaction product of a silane modifier and a vinyl terminated siloxane backbone additive. The precursor may be a reaction product of a silane modifier and a hydroxy terminated siloxane backbone additive. The precursor may be a reaction product of a silane modifier and a hydride terminated siloxane backbone additive. The precursor may be a reaction product of a silane modifier and a TV. The precursor may be a reaction product of a silane. The precursor may be a reaction product of a silane modifier and a cyclosiloxane, taking steric hindrance into account. The precursor may be a partially hydrolyzed tetraethyl orthosilicate such as TES40 or Silbond40. It may be a methyl sesquisiloxane such as SR-350 available from Momentive (formerly General Electric Company, Wilton, Connecticut). The precursor may be a phenyl methyl siloxane such as 604 from Wacker Chemie AG. The precursor may be a methyl phenyl vinyl siloxane such as H62C from Wacker Chemie AG.
[0488] The precursor may also be selected from: SiSiB® HF2020, trimethylsilyl terminated methylhydrogen silicone fluid 63148-57-2; SiSiB® HF2050 trimethylsilyl terminated methylhydroxysiloxane dimethylsiloxane copolymer 68037-59-2; SiSiB® HF2060 hydride terminated methylhydrosiloxane dimethylsiloxane copolymer 69013-23-6; SiSiB® HF2038 hydrogen terminated polydiphenylsiloxane; SiSiB® HF2068 Hydride Terminated Methylhydrosiloxane Dimethylsiloxane Copolymer 115487-49-5; SiSiB® HF2078 Hydrogen Terminated Poly(phenyldimethylsiloxane) Siloxane Silsilsquioxane, Hydrogen Terminated 68952-30-7; SiSiB® VF6060 Vinyldimethyl Terminated Vinylmethyldimethyl Polysiloxane Copolymer 68083-18-1; SiSiB® VF6862 Vinyldimethyl Terminated Dimethyldiphenyl Polysiloxane Copolymer 68951-96-2; SiSiB® VF6872 Vinyldimethyl Terminated Dimethyl-Methyl-Vinyl-Diphenyl Polysiloxane Copolymer; SiSiB® PC9401 1,1,3,3-Tetramethyl-1,3-divinylsiloxane 2627-95-4; SiSiB® PF1070 silanol terminated polydimethylsiloxane (OF1070) 70131-67-8; SiSiB® OF1070 silanol terminated polydimethylsiloxane 70131-67-8; OH terminated polydimethylsiloxane hydroxy terminated oligodimethylsiloxane 73138-87-1; SiSiB® VF6030 vinyl terminated polydimethylsiloxane 68083-19-2; and, SiSiB® HF2030 hydrogen terminated polydimethylsiloxane fluid 70900-21-9.
[0489] Thus, in addition to precursors of the types previously described, it is believed that the precursor may be a compound of the general formula: JPEG2025024179000037.jpg3767
[0490] The end cappers E1 and E2 are selected from the group of trimethylsilyl (trimethylsilicon) (-Si(CH3)3), dimethylsilylhydroxy (dimethylsiliconhydroxy) (-Si(CH3)2OH), dimethylhydridosilyl (dimethylsiliconhydride) (-Si(CH3)2H), dimethylvinylsilyl (dimethylvinylsilicon) (-Si(CH3)2(CH=CH2)), dimethylphenylsilyl (-Si(CH3)2(C6H5)) and dimethylalkoxysilyl (dimethylalkoxysilicon) (-Si(CH3)2(OR). The R groups R1, R2, R3, and R4 can all be different. some may be the same as R3 and R3 may be the same as R4, R1 and R2 may be different and R3 and R4 may be the same, etc. The R groups are selected from groups such as hydrido (-H), methyl (Me)(-C), ethyl (-CC), vinyl (-C=C), alkyl (-R)(CnH2n+1), aryl (-CC=C), aryl (`R), phenyl (Ph)(-C6H5), methoxy (-OC), ethoxy (-OCC), siloxy (-O-Si-R3), alkoxy (-OR), hydroxy (-OH), phenylethyl (-CC-C6H5) and methyl, phenylethyl (-CC(-C)(-C6H5).
[0491] In general, embodiments of polysilocarb formulations have, for example, about 0% to 50% MHF, about 20% to about 99% MHF, about 0% to about 30% siloxane backbone material, about 20% to about 99% siloxane backbone material, about 0% to about 70% reactive monomer, about 0% to about 95% TV, about 0% to about 70% non-silicon based crosslinker, and about 0% to about 90% reaction product of siloxane backbone additive with silane modifier or organic modifier.
[0492] In mixing the formulation, a sufficient time should be used to effectively mix and disperse the precursors. Generally, mixing for about 15 minutes to an hour is sufficient. Typically, the precursor formulations are relatively, and by nature, not shear sensitive, so the type of pump or mixing is not critical. Additionally, more viscous formulations may require additional mixing time. The temperature of the formulation during mixing should preferably be maintained below about 45°C, preferably about 10°C. (These mixing conditions are for pre-catalyzed formulations.) Reaction-type processes
[0493] Reaction-type processes generally use chemical reactions to combine one, two or more precursors, typically in the presence of a solvent, to form a precursor formulation that is essentially comprised of a single polymer, which is then catalyzed, cured, and pyrolyzed. This process offers the ability to build custom precursor formulations that, when cured, can provide plastics with unique and desirable properties. The cured material can also be pyrolyzed to form ceramics with unique characteristics. This reaction-type process allows for a predefined balance of different types of functionality in the final product by selecting the functional groups to be incorporated into the polymers that make up the precursor formulation, such as functional groups such as phenyl, which is not typically used in ceramics but offers the advantage of providing high temperature functionality to plastics, or styrene, which is not typically used in plastics but offers the advantage of providing high temperature functionality to ceramics.
[0494] Typically, custom polymers for use as precursor formulations are made by reacting precursors in a condensation reaction to form a polymer precursor formulation. This precursor formulation is then cured into a preform, i.e., a plastic, hardened solid or semi-solid material, by a hydrolysis reaction. The condensation reaction forms the following types of polymers: JPEG2025024179000038.jpg37127
[0495] R1 and R2 in the polymer unit can be hydride (-H), methyl (Me) (-C), ethyl (-CC), vinyl (-C=C), alkyl (-R) (CnH2n+1), unsaturated alkyl (-C n H 2n-1 ), cyclic alkyl (-C n H 2n-1 ), allyl (-CC=C), butenyl (-C4H7), pentenyl (-C5H9), cyclopentenyl (-C5H7), methylcyclopentenyl (-C5H6(CH3)), norbornenyl (-C X H Y , X=7-15 and Y=9-18), allyl (`R), phenyl (Ph) (-C6H5), cycloheptenyl (-C7H 11 ), cyclooctenyl (-C8H 13 ), ethoxy (-OCC), siloxy (-O-Si-R3), methoxy (-OC), alkoxy, (-OR), hydroxy, (-OH), phenylethyl (-CC-C6H5), methyl, phenyl-ethyl (-CC(-C)(-C6H5)) and vinylphenyl-ethyl (-CC-C6H4(-C)=C)). R1 and R2 can be the same or different. The custom precursor polymers are A1, A2, A3, A4, A5, A6, A7, A8, A9, A10, A11, A12, A13, A14, A15, A16, A17, A18, A19, A20, A21, A22, A23, A24, A25, A26, A27, A28, A29, A30, A31, A32, A33, A34, A35, A36, A37, A38, A39, A40, A41, A42, A43, A44, A45, A46, A47, A48, A49, A50, A51, A52, A53, A54, A55, A56, A57, A58, A59, A60, A61, A62, A63, A64, A65, A65, A66, A67, A68, A69, A70, A71, A72, A73, A74, A75, A75, A75, A76, A77, A78, A79, A71, A72, A75, A78, A79, A71, A72, A73, A74, A75, A75, A76, A77, A78, A79, A79, A71, A72, A74, n Such polymeric units may have several different polymer units such as , may contain 10, 20 or more units, or may contain only a single unit such as MHF that is created by a reactive process.
[0496] Embodiments can include precursors including, among others, triethoxymethylsilane, diethoxymethylphenylsilane, diethoxymethylhydridosilane, diethoxymethylvinylsilane, dimethylethoxyvinylsilane, diethoxydimethylsilane, ethoxydimethylphenylsilane, diethoxydihydridosilane, triethoxyphenylsilane, diethoxyhydridotrimethylsiloxane, diethoxymethyltrimethylsiloxane, trimethylethoxysilane, diphenyldiethoxysilane, dimethylethoxyhydridosiloxane, and combinations and variations of these and other precursors including other precursors described herein.
[0497] The end units, SiEnd1 and SiEnd2, can be derived from the precursors dimethylethoxyvinylsilane, ethoxydimethylphenylsilane, and trimethylethoxysilane. Additionally, if the polymerization process is properly controlled, hydroxy end caps can be obtained from the precursors used to provide the repeat units of the polymer.
[0498] Typically, the precursor is added to a vessel along with ethanol (or other material that absorbs heat, e.g., provides thermal mass), excess water, and hydrochloric acid (or other proton source). The mixture is heated until an activation energy is reached, after which the reaction is typically exothermic. Typically, in this reaction, water reacts with an ethoxy group on the silane of the precursor monomer to form a hydroxyl (with ethanol as a byproduct). Once formed, this hydroxyl reacts with an ethoxy group on the silicon of another precursor monomer, causing a polymerization reaction. This polymerization reaction is continued until the desired chain length is built.
[0499] Among other things, the controlling factors for determining the chain length are: the monomer selected (generally, the smaller the monomer, the more it can be added before it starts to wrap around and bond to itself); the amount and point in the reaction where the end capper is introduced; and the amount and especially the rate of addition of water. Thus, chain lengths can range from about 180 mw (viscosity about 5 cps) to about 65,000 mw (viscosity about 10,000 cps), to greater than about 1000 mw, to greater than about 10,000 mw, to greater than about 50,000 mw. Additionally, the polymerized precursor formulation may, and usually does, have polymers of different molecular weights, which can be predetermined to provide performance characteristics for the formulation, the cured product, and the ceramic product.
[0500] Once the polymerization reaction is complete, the material is transferred to a separation device, such as a separatory funnel, with deionized water in an amount of, for example, about 1.2 to about 1.5 times the mass of the material. The mixture is vigorously stirred for less than 1 minute, preferably about 5 to 30 seconds. After stirring, the material settles and separates, which takes about 1 to 2 hours. The polymer is the denser material and is removed from the vessel. This removed polymer is dried by placing in a shallow tray and warming at 90°C for about 2 hours. Alternatively, it is preferably passed through a wiped film distillation apparatus to remove any residual water and ethanol. Alternatively, enough sodium bicarbonate is added to buffer the aqueous layer to a pH of about 7 to about 4. It should be noted that other commercial methods of mixing the materials, reacting, and isolating the polymer can be used.
[0501] Preferably, a catalyst is used in the curing process of the polymer precursor formulation from the reactive process. The same polymers can be used as those used in the curing of the precursor formulation from the mixed process. In general, unlike the mixed type formulation, a catalyst is not necessarily required to cure the reactive type polymer. An inhibitor can also be used. However, if a catalyst is not used, the reaction time and reaction rate will be slower. The curing and pyrolysis of the cured material from the reactive process is essentially the same as that of the cured material from the mixed process and the reactive mixed process.
[0502] Reactive processes can be carried out under many types of atmospheres and conditions, such as, for example, air, inert gas, N2, argon, flowing gas, static gas, reduced pressure, ambient pressure, elevated pressure, and combinations and variations thereof. Reactive Mixture Process
[0503] In a reactive blending type process, precursors react in the absence of a solvent to form a precursor formulation. For example, an embodiment of a reactive blending type process has a precursor formulation prepared from MHF and dicyclopentadiene (DCPD). Using a reactive blending process, a MHF / DCPD polymer is made, which is used as a precursor formulation, which alone forms a cured or pyrolyzed product, or is used as a precursor in a blending or reaction process.
[0504] Thus, for example, about 40 to 90% MHF of known molecular weight and hydride equivalent weight; about 0.20 wt% PO1 catalyst; and about 10-60% DCPD of 83% or greater purity can be used.
[0505] P01 is a 2% Pt(0) tetravinylcyclotetrasiloxane complex in tetravinylcyclotetrasiloxane diluted 20 times with tetravinylcyclotetrasiloxane to 0.1% Pt(0) complex. This method delivers 10 ppm Pt for every 1% loading of bulk cat.
[0506] In an embodiment of the process, a sealable reaction vessel equipped with a mixer can be used for the reaction. The reaction takes place in air in a sealed vessel, although other types of atmospheres can be utilized. Preferably, the reaction is carried out at atmospheric pressure, although higher and lower pressures can be utilized. Additionally, reaction mixing type processes can be carried out under many types of atmospheres and conditions, including air, inert gas, N2, argon, flowing gas, static gas, reduced pressure, atmospheric pressure, elevated pressure, and combinations and variations of these.
[0507] In one embodiment, 850 grams of MHF (85% of the total polymer mixture) is added to a reaction vessel and heated to approximately 50° C. Once this temperature is reached, the heater is turned off and 0.20% (by weight of MHF) of P01 platinum catalyst is added to the MHF in the reaction vessel. Typically, gas bubbles form and the temperature initially rises by approximately 2-20° C. as the catalyst is added.
[0508] When the temperature begins to drop, add approximately 150 g of DCPD (15 wt % of total polymer mixture) to the reaction vessel. The temperature may drop further (e.g., to approximately 5-7° C.).
[0509] At this point in the reaction process, the temperature of the reaction vessel is controlled to maintain a predetermined temperature profile over time and to manage any temperature increases that may accompany the exotherm. Preferably, the temperature of the reaction vessel is regulated, monitored, and controlled throughout the process.
[0510] In an MHF / DCPD embodiment of the reaction process, the temperature profile can be as follows: allow the temperature to reach approximately 80°C (which can take approximately 15-40 minutes depending on the amount of material present); then the temperature increases, peaking at ~104°C, and as soon as the temperature begins to drop, increase the heater set point to 100°C and monitor the temperature of the reaction mixture to allow the temperature of the polymer to exceed 80°C for a minimum of approximately 2 hours total and a maximum of approximately 4 hours total. After 2-4 hours above 80°C, turn off the heater and allow the polymer to cool to ambient temperature. Temperature and time profiles may vary for small and large batch, continuous, semi-continuous, and other types of processes.
[0511] Large scale and commercial operations can use batch, continuous, and combinations of these. Industrial plant automation and control systems can be utilized to control the reaction, temperature profile, and other processes during the reaction.
[0512] Table A shows various embodiments of the precursor materials.
[0513] Table A JPEG2025024179000039.jpg100121
[0514] In the above table, "degree of polymerization" is the number of monomeric or repeating units that combine together to form a polymer. "Equivalents / mol" refers to the molar equivalent. "Grams of vinyl / mole" refers to the amount of a given polymer needed to provide one molar equivalent of vinyl functionality. "VMH" refers to methyl vinyl fluids, an ethoxy process linear vinyl material that can be used in place of TV. VT numbers such as "0200" are the viscosity in centipoise of that particular VT (e.g. 0200=200cps). Hardening and pyrolysis
[0515] Precursor formulations, including polysilocarb precursor formulations from the above types of processes and other processes, can be cured to form solid, semi-solid, or plastic-like materials. Typically, the precursor formulations are spread, molded, or otherwise formed into preforms, including any volumetric structure or shape, including thin and thick films. During curing, the polysilocarb precursor formulations can be treated with an initial cure to provide, for example, a preform, a green material, or a partially cured material, also called a green cure (which does not imply anything about the color of the material). The green material can then be further cured. Thus, one or more curing steps can be used. The material can be "final cured," i.e., cured to a point where the material has the physical strength and other properties required for its intended purpose. The amount of curing can be to a final cure (or "hard cure"), i.e., a point where all, or essentially all, of the chemical reactions have stopped (this can be determined, for example, by the absence of reactive groups in, i.e., all reactions have stopped, or by measuring a plateau in the reduction of reactive groups over time, i.e., essentially all reactions have stopped). Thus, a material can be cured to various degrees depending on its intended use and purpose. For example, in some situations, the final cure and the hard cure may be the same thing. The curing conditions, such as atmosphere and temperature, may affect the composition of the cured material.
[0516] In multi-layer or composite structures and configurations, the layers of polysilocarb material can be cured to different degrees, for example, in multi-layer embodiments, the layers can be green cured to promote adhesion of the layers and then final cured. Each layer within a multi-layer structure can be cured to the same degree, different degrees of cure, using one, two, three or more curing steps, and combinations and variations thereof.
[0517] Curing can occur at standard ambient temperature and pressure ("SATP", 1 atmosphere, 25°C), at temperatures above or below that temperature, at pressures above or below that pressure, and for various durations. Curing can be performed with a variety of heating, heating rates, and temperature profiles (e.g., hold times and temperatures, continuous temperature changes, cyclic temperature changes, e.g., heating followed by holding, cooling, reheating, etc.). Curing times can range from a few seconds (e.g., less than about 1 second, less than 5 seconds), to less than a minute, to several minutes, to several hours, to days (or potentially longer). Curing can also be carried out in any type of ambient environment including, for example, gas, liquid, air, water, surfactant containing liquid, inert atmosphere, N2, argon, flowing gas (e.g., sweep gas), static gas, reduced O2 (e.g., an amount of O2 less than atmospheric pressure, e.g., less than 20% O2, less than 15% O2, less than 10% O2, less than 5% O2), reduced pressure (e.g., less than atmospheric pressure), high pressure (e.g., greater than atmospheric), enriched O2 (e.g., an amount of O2 greater than atmospheric), ambient pressure, controlled partial pressure, and combinations and variations of these and other process conditions.
[0518] In one embodiment, the curing environment, e.g., furnace, atmosphere, vessel, and combinations and variations thereof, can have materials that contribute to or affect the composition, catalysis, stoichiometry, characteristics, performance, and combinations and variations thereof, for example, in the preform, cured material, ceramic, end use or product.
[0519] For high purity materials, the furnaces, vessels, handling equipment, atmosphere, and other components of the curing apparatus and process are clean and essentially free of and do not contribute to the cured material elements or materials that would be considered impurities or contaminants.
[0520] Preferably, in embodiments of the curing process, curing occurs at temperatures ranging from about 5° C. or higher, from about 20° C. to about 250° C., from about 20° C. to about 150° C., from about 75° C. to about 125° C., and from about 80° C. to 90° C. Higher and lower temperatures and various heating profiles (e.g., rate of temperature change over time ("ramp rate", e.g., Δ degrees / hour), hold times, and temperatures) can be utilized.
[0521] The curing conditions, e.g., temperature, time, ramp rate, can be wholly or partially dependent on and in some embodiments predetermined by the formulation, e.g., matching the size of the preform, the shape of the preform, or the mold holding the preform, to prevent stress cracking, outgassing, or other phenomena associated with the curing process. Furthermore, the curing conditions can be such that they take advantage of previously recognized problems associated with the curing process, preferably in a controlled manner. Thus, for example, outgassing can be used to create foamed materials with either open or closed structures. Similarly, the curing conditions can be used to create or control the microstructure and nanostructure of the material. In general, the curing conditions can be used to affect, control, or modify the reaction kinetics and thermodynamics in the process. This can affect morphology, performance, characteristics, function, etc.
[0522] Curing the polysilocarb precursor formulation, in some embodiments, results in a crosslinking reaction that provides, among other things, a crosslinked structure having, for example, -R1-Si-C-C-Si-O-Si-C-C-Si-R2-, where R1 and R2 vary depending on and based on the precursors used in the formulation. In embodiments of the cured materials, they may have a crosslinked structure having a silicon center in three-coordinated relation to another silicon atom, separated by less than five atoms between the silicon atoms. Additional other structures and types of cured materials are also contemplated. Thus, for example, using Luperox231 results in a structure that is -Si-CCC-Si- from the same monomer. When other crosslinkers are used, such as DCPD and divinylbenzene, the number of carbon atoms between the silicon atoms is greater than five atoms. A generalized formula for some embodiments of the crosslinked, e.g., cured, material is -Si-R3-Si-, where R3 is ethyl (e.g., from a vinyl precursor), propyl (e.g., from an allyl precursor), dicyclopentane (e.g., from a DCPD precursor), norbornane (e.g., from a norbornadiene precursor), diethylbenzene (e.g., from a divinylbenzene precursor), and the like.
[0523] During the curing process, some formulations may generate exotherms, i.e., self-heating reactions that can generate small amounts of heat to assist or drive the curing reaction, or large amounts of heat that may require management and removal to avoid issues such as stress fracture. Emissions are typically generated during curing, resulting in material loss, i.e., the amount of material remaining, a loss defined by, for example, cure yield. Formulations, cure conditions, and polysilocarb precursor formulation embodiments of the present invention may have cure yields of at least about 90%, about 92%, about 100%. Indeed, in air curing, as a result of oxygen being absorbed from the air, materials may have cure yields of greater than 100%, for example, about 101-105%. Additionally, materials will typically shrink during curing, but this shrinkage can be about 20%, less than 20%, less than about 15%, less than about 5%, less than about 1%, less than about 0.5%, less than about 0.25%, and less depending on the formulation, the curing conditions, the nature of the preform shape, and whether the preform is reinforced, filled, neat, or unreinforced.
[0524] Curing can be accomplished by any type of heating device, or mechanism, technique, or form that has the required level of temperature and environmental control, such as heated water baths, electric ovens, microwaves, gas ovens, furnaces, forced heated air, towers, spray drying, falling film reactors, fluidized bed reactors, indirect heating elements, direct heating (e.g., heated surfaces, drums, and plates), infrared heating, UV irradiation (light), RF ovens, in situ emulsification by high shear mixing, in situ emulsification by sonication, broadband white light, IR light, coherent electromagnetic radiation (e.g., lasers including visible, UV, and IR), convection heating, and the like.
[0525] In one embodiment, with sufficient amounts of catalyst, curing can also occur under atmospheric conditions.
[0526] When pyrolysis in one embodiment is performed, the hardened material can be heated, for example, to about 600°C to about 2300°C, about 650°C to about 1,200°C, about 800°C to about 1300°C, about 900°C to about 1,200°C, and about 950°C to 1,150°C. At these temperatures, typically all organic structures are removed or combined with inorganic components to form a ceramic. Typically, at temperatures in the range of about 650°C to 1,200°C, the resulting material is an amorphous glass-ceramic. When heated to temperatures above about 1,200°C, the material typically forms nanocrystalline or microcrystalline structures such as SiC, Si3N4, SiCN, βSiC, and αSiC structures at 1,900°C and above, and αSiC typically forms at 2,200°C and above. The pyrolyzed, for example, ceramic material can be monocrystalline, polycrystalline, amorphous, and combinations, variations, and subgroups of these and other types of morphologies.
[0527] Pyrolysis can be carried out under many different heating and environmental conditions, preferably including, among others, thermal control, rate control, and combinations and variations thereof. For example, pyrolysis has a variety of heating ramp rates, heating cycles, and environmental conditions. In some embodiments, the temperature can be raised and held at a given temperature to assist in a known transition (e.g., gas evolution, volatilization, molecular rearrangement, etc.), and then increased to a next hold temperature corresponding to the next known transition. Pyrolysis can occur in reducing atmosphere, oxidizing atmosphere, low O2, gas rich (e.g., within a flame or directly adjacent to a flame), inert, N2, argon, air, reduced pressure, ambient pressure, high pressure, flowing gas (e.g., sweep gas with flow rates of about 15.0 GHSV (gas hourly space velocity) to about 0.1 GHSV, about 6.3 GHSV to about 3.1 GHSV, and about 3.9 GHSV), static gas, and combinations among these variations.
[0528] In some embodiments, upon pyrolysis, graphene, graphite, amorphous carbon structures, and combinations and variations thereof are present in the Si-OC ceramic. The distribution of silicon species consisting of SiOxCy structures resulting in SiO4, SiO3C, SiO2C2, SiOC3, and SiC4 is formed in various ratios from the choice of precursors and their processing history. Carbon is usually bonded between adjacent carbon and / or silicon atoms. Generally, in the ceramic state, carbon is rarely coordinated to oxygen atoms, while oxygen is heavily coordinated to silicon.
[0529] Pyrolysis can be carried out in any heating device that maintains the required temperature and environmental control. Thus, for example, pyrolysis can be carried out in pressure furnaces, box furnaces, tube furnaces, crystal growth furnaces, graphite box furnaces, arc melting furnaces, induction furnaces, kilns, MoSi2 heating element furnaces, carbon furnaces, vacuum furnaces, gas furnaces, electric furnaces, direct heat, indirect heat, fluidized bed, RF furnaces, kilns, tunnel kilns, box kilns, shuttle kilns, coking equipment, lasers, microwaves, other electromagnetic radiation, and combinations and variations of these and other heating devices and systems capable of obtaining the required temperature for pyrolysis.
[0530] In embodiments of the polysilocarb-derived ceramic material, the amount of Si, O, or C relative to the total amount of material listed in Table B is included.
[0531] Table B JPEG2025024179000040.jpg45152
[0532] In general, embodiments of the pyrolyzed ceramic polysiloxane material can have from about 20% to about 65% Si, from about 5% to about 50% O, and from about 3% to about 55% carbon weight percent. Higher and lower amounts are also contemplated.
[0533] Generally, embodiments of the pyrolyzed ceramic polysilocarb material can have a molar ratio of Si from about 0.5 to about 2.5 (based on total Si, O, and C), a molar ratio of O from about 0.2 to about 2.5, and a molar ratio of C from about 0.1 to about 4.5. Higher and lower amounts are contemplated.
[0534] In general, embodiments of the pyrolytic ceramic polysilocarb material can have a molar % of Si (proportions of total Si, O, and C) of about 13% to about 68%, a molar % of O of about 6% to about 60%, and a molar % of C of about 4% to about 75%. Higher and lower amounts are contemplated.
[0535] The type of carbon present in the polysilocarb-derived ceramic pigment embodiments can be free carbon (e.g., turbostratic, amorphous, graphene, graphite forms of carbon) and silicon-bonded carbon. Ceramic polysilocarb material embodiments having free carbon and silicon-bonded carbon (Si-C) are described in Table C. Larger and smaller amounts and different ratios of free carbon and silicon-bonded carbon are also contemplated.
[0536] Table C JPEG2025024179000041.jpg118137
[0537] In general, embodiments of the polysilocarb derived ceramic material can have about 30% free carbon to about 70% free carbon, about 20% free carbon to about 80% free carbon, and about 10% free carbon to about 90% free carbon, and about 30% Si-C bonded carbon to about 70% Si-C bonded carbon, about 20% Si-C bonded carbon to about 80% Si-C bonded carbon, and about 10% Si-C bonded carbon to about 90% Si-C bonded carbon. Higher and lower amounts are also contemplated. Metals and Metal Complexes
[0538] As an example, metals and metal complexes that can be used as filler materials would include cyclopentadienyl compounds of available transition metals. Cyclopentadienyl compounds of transition metals can be divided into two classes: biscyclopentadienyl complexes; and monocyclopentadienyl complexes. Cyclopentadienyl complexes can include CH, CMe, CHMe, CHR (where R = Me, Et, Propyl, i-Propyl, Butyl, Isobutyl, Sec-Butyl). In each of these cases, Si is either directly bonded to the cyclopentadienyl ligand or the Si center is bonded to an alkyl chain that is in turn bonded to the cyclopentadienyl ligand.
[0539] Cyclopentadienyl complexes that can be utilized with the precursor formulation and in the product can include: bis-cyclopentadienyl metal complexes of first row transition metals (titanium, vanadium, chromium, iron, cobalt, nickel); second row transition metals (zirconium, molybdenum, ruthenium, rhodium, palladium); third row transition metals (hafnium, tantalum, tungsten, iridium, osmium, platinum); the lanthanide series (La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho); and the actinide series (Ac, Th, Pa, U, Np).
[0540] Monocyclopentadienyl complexes can also be utilized to provide metal functionality to the precursor formulation, including monocyclopentadienyl complexes of first row transition metals (titanium, vanadium, chromium, iron, cobalt, nickel); second row transition metals (zirconium, molybdenum, ruthenium, rhodium, palladium); and, preferably stabilized with an appropriate ligand (e.g., chloride or carbonyl), third row transition metals (hafnium, tantalum, tungsten, iridium, osmium, platinum).
[0541] Metal alkyl complexes can also be used to provide metal functionality to precursor formulations and products. In these alkyl complexes, the Si center has an alkyl group (ethyl, propyl, butyl, vinyl, propenyl, butenyl) that can bond directly to the transition metal via a sigma bond. Furthermore, this is more common for later transition metals such as Pd, Rh, Pt, and Ir.
[0542] Coordination complexes of metals can also be used to provide metal functionality to precursor formulations and products. In these coordination complexes, the Si center has an unsaturated alkyl group (vinyl, propenyl, butenyl, acetylene, butadienyl) that can be bonded to carbonyl or ene complexes of Cr, Mo, W, Mn, Re, Fe, Ru, Os, Co, Rh, Ir, Ni. The Si center may also be bonded to phenyl, substituted phenyl, or other aryl compounds (pyridine, pyrimidine), where the phenyl or aryl group can replace the carbonyl on the metal center.
[0543] Metal alkoxides can also be used to provide metal functionality to the precursor formulations and products. Metal alkoxide compounds can be mixed with silicon precursor compounds and treated with hydroxides to form oxides as the polymers copolymerize. This can also be done with metal halides and metal amides. Preferably, this can be done with early transition metals and aluminum, gallium and indium, late transition metals: Fe, Mn, Cu, and alkaline earth metals: Ca, Sr, Ba, Mg.
[0544] Compounds in which Si is directly bonded to a metal center stabilized by a halide or organic group can also be utilized to provide metal functionality to precursor formulations and products.
[0545] Additionally, it is understood that the metals and metal complexes may be continuous phases after pyrolysis or subsequent heat treatment. The formulations may be specifically designed to react with selected metals to form in situ metal carbides, oxides, and other metal compounds (such as ceramic metal compounds) commonly known as cermets. The formulations may be reacted with selected metals to form in situ compounds such as mullite, aluminosilicates, and the like. The amount of metal relative to the amount of silica in the formulation or final product may be about 0.1 mol% to 99.9 mol%, about 1 mol% or more, about 10 mol% or more, and about 20 mol% or more. The aforementioned use of metals having the precursor formula of the present invention may be used to control and provide a predetermined stoichiometry. Heading and embodiment
[0546] The use of headings herein is for purposes of clarity and is in no way limiting. Thus, the processes and disclosures described under the headings should be read in conjunction with the entire specification, including the various examples. The use of headings herein does not limit the scope of protection afforded to the present invention.
[0547] It should be noted that it is not necessary to provide or refer to the theory underlying the novel and breakthrough process, material, performance, or other beneficial features and characteristics that are the subject of or related to the embodiments of the present invention. Nevertheless, various theories are provided herein to further advance the art in this field. These theories described herein in no way restrict, limit or narrow the scope of protection afforded to the claimed invention, unless specifically stated otherwise. Many of these theories are not required or adhered to in order to utilize the present invention. Furthermore, it is understood that the present invention may lead to novel and previously unknown theories for explaining the functional characteristics of the embodiments of the methods, articles, materials, devices, and systems of the present invention. And such subsequently developed theories shall not limit the scope of protection of the present invention.
[0548] The various embodiments of the formulations, compositions, articles, plastics, ceramics, materials, parts, wafers, boules, volumetric structures, applications, uses, equipment, methods, activities, and operations described herein can be used in a variety of applications. Other fields and various other activities, applications, and embodiments. Furthermore, these embodiments may be used, for example, in existing systems, articles, formulations, materials, operations, or activities. They may be used in systems, articles, formulations, materials operations, or activities that may be developed in the future. Also, such systems, articles, formulations, materials, operations, or activities may be modified in part based on the teachings of this specification. Furthermore, the various embodiments and examples described herein may be used in whole or in part with each other and in various combinations. Thus, for example, the configurations provided in the various embodiments and examples herein may be used with each other. And the scope of protection given to the present invention should not be limited to the specific embodiments, examples, configurations, or arrangements described in the specific embodiments, examples, or embodiments of the specific figures.
Claims
[Claim 1] 1. A starting material for use in a deposition process for growing a SiC boule, comprising: a. D from 0.1 μm to 20.0 μm 50 100 g to 12,000 g of SiC granules having a particle size of b. a binder that binds the SiC granules together; c. the binder and the SiC granules define a volume shape having structural integrity; d. the binder is less than 35% by weight of the volume shape; e. the volumetric shape has an outer diameter defining an opening; f. the volume shape has voids defining porosity, whereby the volume shape has an apparent density of less than 3.0 g / cc; g. the opening has a cross-section of at least 1 / 4 inch (6.35 mm); h. the opening: i. disposed on top of the volumetric shape; ii. disposed at the bottom of the volumetric shape; iii. a channel in the volumetric shape; iv. a cylindrical channel extending through the volume; The starting material is one or more of:
Citation Information
Patent Citations
Silicon carbide production process and silicon carbide
JP2014162686A
Polysilocarb based silicon carbide materials, applications and devices
WO2016049344A2